Polarizer and image display device

A polarizer with a liquid crystal compound and arrayed dichroic substances addresses the inefficiencies of conventional polarizers by enhancing orientation and spectral control, improving image display devices.

JP7607728B2Active Publication Date: 2024-12-27FUJIFILM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023191392
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-30
Filing Date
2023-11-09
Publication Date
2024-12-27
Estimated Expiration
2039-03-27

AI Technical Summary

Technical Problem

Conventional polarizers require different manufacturing processes for each optical function, such as attenuation, polarization, and scattering, limiting the integration and efficiency of light control in devices like liquid crystal displays and OLEDs, and existing polarizers with organic dyes need improvements in orientation.

Method used

A polarizer formed from a composition containing a liquid crystal compound and two dichroic substances arranged in an array structure, enhancing the degree of orientation and absorption spectrum differences.

Benefits of technology

The array structure improves the degree of orientation and spectral control, allowing for higher performance and versatility in image display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607728000043
    Figure 0007607728000043
  • Figure 0007607728000044
    Figure 0007607728000044
  • Figure 0007607728000045
    Figure 0007607728000045
Patent Text Reader

Abstract

To provide a polarizer with a high orientation, and an image display device having the polarizer.SOLUTION: The polarizer of the present invention is a polarizer formed of a polarizer forming composition including a liquid crystal compound, a first dichroic substance, and a second dichroic substance. The polarizer also has an alignment structure formed of the first and second dichroic substances.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizer and an image display device. [Background technology]

[0002] Conventionally, when it became necessary to attenuate, polarize, scatter, or block irradiated light, including laser light or natural light, devices that operated on different principles for each function were used. Therefore, products corresponding to the above functions were also manufactured using different manufacturing processes for each function. For example, in image display devices (e.g., liquid crystal display devices), linear or circular polarizers are used to control the optical rotation or birefringence in display. Also, in organic light emitting diodes (OLEDs), circular polarizers are used to prevent reflection of external light.

[0003] Conventionally, iodine has been widely used as a dichroic material in these polarizers, but polarizers using an organic dye as a dichroic material instead of iodine are also being considered. For example, Patent Document 1 discloses a composition for forming a polarizer, which contains a polymer liquid crystal compound and a dichroic substance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 154907 Summary of the Invention [Problem to be solved by the invention]

[0005] In this situation, the inventors produced a polarizer by reference to the examples in Patent Document 1 and evaluated its degree of orientation. In view of expected future improvements in the performance of image display devices and the like, it became clear that it would be desirable to further improve the degree of orientation.

[0006] In view of the above circumstances, an object of the present invention is to provide a polarizer having a high degree of orientation and an image display device having the polarizer. [Means for solving the problem]

[0007] As a result of intensive research into the above-mentioned problems, the inventors have found that the degree of orientation can be improved when a polarizer formed from a polarizer-forming composition containing a liquid crystal compound, a first dichroic substance, and a second dichroic substance has an arrangement structure formed from the first dichroic substance and the second dichroic substance, and have thus arrived at the present invention. That is, the present inventors have found that the above problems can be solved by the following configuration.

[0008] [1] A polarizer formed from a composition for forming a polarizer, the composition containing a liquid crystal compound, a first dichroic substance, and a second dichroic substance, a polarizer having an alignment structure formed from the first dichroic material and the second dichroic material. [2] The polarizer according to [1], wherein in the arrangement structure, the first dichroic material and the second dichroic material form an association. [3] a maximum absorption wavelength λ2 in an absorption spectrum of a film formed from a composition that does not contain the first dichroic material and contains the second dichroic material and the liquid crystal compound; and a maximum absorption wavelength λ in a difference spectrum between an absorption spectrum of the polarizer and an absorption spectrum of a film formed from a composition that does not contain the second dichroic material and contains the first dichroic material and the liquid crystal compound; and The polarizer according to [1] or [2], wherein the absolute value of the difference is greater than 2 nm. [4] a maximum absorption wavelength λ4 in an absorption spectrum of a film formed from a composition that does not contain the second dichroic material and contains the first dichroic material and the liquid crystal compound; and The maximum absorption wavelength λ1 in the absorption spectrum of the polarizer; The polarizer according to any one of [1] to [3], wherein the absolute value of the difference is greater than 2 nm. [5] The polarizer according to any one of [1] to [4], wherein in the arrangement structure, the first dichroic material and the second dichroic material form a crystal structure. [6] the intensity of a peak O1 of a periodic structure originating from the second dichroic material in an X-ray diffraction spectrum of the polarizer; and the intensity of a peak O2 of a periodic structure derived from the second dichroic material in an X-ray diffraction spectrum of a film formed from a composition that does not contain the first dichroic material and contains the second dichroic material and the liquid crystal compound; and The polarizer according to any one of [1] to [5], wherein [7] The polarizer according to [6], wherein a ratio of an intensity of the peak O1 to an intensity of the peak O2 is less than 1. [8] When the X-ray diffraction spectrum of the polarizer was measured, The polarizer according to any of [1] to [7], wherein a peak OM of the periodic structure derived from the first dichroic material and the second dichroic material is detected at a diffraction angle different from a diffraction angle at which a peak M2 of the periodic structure derived from the first dichroic material is detected in an X-ray diffraction spectrum of a film formed from a composition that does not contain the second dichroic material and contains the first dichroic material and the liquid crystal compound, and a diffraction angle at which a peak O2 of the periodic structure derived from the second dichroic material is detected in an X-ray diffraction spectrum of a film formed from a composition that does not contain the first dichroic material and contains the second dichroic material and the liquid crystal compound. [9] The polarizer according to any one of [1] to [8], wherein a stabilization energy representing an energy loss when one of the first dichroic material and the second dichroic material enters a structure in which the other dichroic material is independently arranged is less than 72 kcal / mol.

[10] The polarizer according to [9], wherein the stabilization energy is 55 kcal / mol or less.

[11] The polarizer according to [9] or

[10] , wherein the stabilization energy is 35 kcal / mol or less.

[12] the first dichroic substance is a dichroic substance having a maximum absorption wavelength in the range of 560 nm to 700 nm, The polarizer according to any one of [1] to

[11] , wherein the second dichroic substance is a dichroic substance having a maximum absorption wavelength in the range of 455 nm or more and less than 560 nm.

[13] The polarizer according to any one of [1] to

[12] , wherein an absolute value of a difference between a logP value of a side chain of the first dichroic material and a logP value of a side chain of the second dichroic material is 2.30 or less.

[14] The polarizer according to any one of [1] to

[13] , further comprising a third dichroic substance having a maximum absorption wavelength in the range of 380 nm or more and less than 455 nm.

[15] An image display device comprising the polarizer according to any one of [1] to

[14] . Effect of the Invention

[0009] As will be described below, according to the present invention, a polarizer having a high degree of orientation and an image display device having the polarizer can be provided. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a conceptual diagram showing an example of a state in which a first dichroic material and a second dichroic material form an array structure. [Diagram 2]FIG. 2 is a conceptual diagram showing an example of an arrangement structure of a first dichroic material and a second dichroic material. [Diagram 3] FIG. 2 is a diagram illustrating an example of an absorption spectrum of the polarizer of the present invention. [Figure 4] FIG. 1 shows an XRD (X-ray diffraction) spectrum corresponding to film 1-2. [Diagram 5] FIG. 1 shows the XRD spectrum corresponding to film 1-3. [Figure 6] FIG. 2 shows an XRD spectrum corresponding to the polarizer (Film 1) of Example 1. [Figure 7] FIG. 1 shows the XRD spectrum corresponding to film 2-4. [Figure 8] FIG. 13 shows the XRD spectrum corresponding to film 2-2. [Figure 9] FIG. 13 shows the XRD spectrum corresponding to film 2-3. [Figure 10] FIG. 13 shows an XRD spectrum corresponding to the polarizer (Film 2) of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In addition, each component may be used alone or in combination of two or more. When two or more components are used in combination, the content of the components refers to the total content unless otherwise specified. In addition, "(meth)acrylate" is a notation that represents "acrylate" or "methacrylate", "(meth)acrylic" is a notation that represents "acrylic" or "methacrylic", and "(meth)acryloyl" is a notation that represents "acryloyl" or "methacryloyl".

[0012] [Polarizer] The polarizer of the present invention is a polarizer formed from a polarizer-forming composition containing a liquid crystal compound, a first dichroic material, and a second dichroic material, and has an arrangement structure formed from the first dichroic material and the second dichroic material. The present inventors have found that the degree of orientation may be high when a polarizer having a first dichroic material and a second dichroic material is manufactured. Upon detailed investigation of the reason for this, it has been found that the degree of orientation is high if the positional relationship between the first dichroic material and the second dichroic material in the polarizer is closely related and the first dichroic material and the second dichroic material form an array structure.

[0013] In the present invention, the arrangement structure formed by the first dichroic material and the second dichroic material means a state in which one or more molecules of the first dichroic material and one or more molecules of the second dichroic material gather together to form an aggregate in a polarizer, and multiple molecules of the dichroic material are periodically arranged in the aggregate. Fig. 1 is a conceptual diagram showing an example of a state in which a first dichroic material and a second dichroic material form an array structure. A polarizer P has a molecule M of the first dichroic material, a molecule O of the second dichroic material, and a molecule L of a liquid crystal compound. As shown in Fig. 1, an aggregate G containing the molecule M and the molecule O is formed, and in the aggregate G, the long axis directions of the molecules M and O are aligned in the same direction, and the molecules M and O are arranged so as to be shifted from each other at a period of width w. The array structure formed by the first dichroic material and the second dichroic material is not limited to the array structure in FIG. 1, and may be arranged such that, for example, molecules M and O are shifted at a period of angle a, as shown in FIG. 2. In the polarizer, the first dichroic material may be polymerized, and similarly, in the polarizer, the second dichroic material may be polymerized.

[0014] [Polarizer-forming composition] The polarizer-forming composition used to form the polarizer of the present invention (hereinafter also referred to as "the composition") contains a liquid crystal compound, a first dichroic substance, and a second dichroic substance. The composition may contain a third dichroic substance, a solvent, a polymerization initiator, an interfacial improver, or other components other than these, as necessary. Each component will be described below.

[0015] <Liquid crystal compounds> The composition contains a liquid crystal compound, which makes it possible to align the dichroic substance with a high degree of orientation while preventing precipitation of the dichroic substance. The liquid crystal compound is a liquid crystal compound that does not exhibit dichroism. As the liquid crystal compound, either a low molecular weight liquid crystal compound or a polymeric liquid crystal compound can be used. Here, the term "low molecular weight liquid crystal compound" refers to a liquid crystal compound that does not have a repeating unit in its chemical structure. The term "polymeric liquid crystal compound" refers to a liquid crystal compound that has a repeating unit in its chemical structure. Examples of the low molecular weight liquid crystal compound include the liquid crystal compounds described in JP-A-2013-228706. Examples of the polymeric liquid crystal compound include the thermotropic liquid crystal polymers described in JP 2011-237513 A. The polymeric liquid crystal compound may have a crosslinkable group (e.g., an acryloyl group or a methacryloyl group) at the end. The liquid crystal compounds may be used alone or in combination of two or more. The content of the liquid crystal compound is preferably 25 to 2000 parts by mass, more preferably 33 to 1000 parts by mass, and further preferably 50 to 500 parts by mass, relative to 100 parts by mass of the content of the dichroic substance in the composition. When the content of the liquid crystal compound is within the above range, the degree of orientation of the polarizer is further improved.

[0016] The liquid crystal compound is preferably a polymer liquid crystal compound containing a repeating unit represented by the following formula (1) (hereinafter also referred to as "repeating unit (1)"), because the effects of the present invention are more excellent.

[0017] [ka]

[0018] In the above formula (1), P1 represents the main chain of the repeating unit, L1 represents a single bond or a divalent linking group, SP1 represents a spacer group, M1 represents a mesogenic group, and T1 represents a terminal group.

[0019] Specific examples of the main chain of the repeating unit represented by P1 include groups represented by the following formulae (P1-A) to (P1-D). Among these, the group represented by the following formula (P1-A) is preferred from the viewpoints of the variety of monomers that serve as raw materials and ease of handling.

[0020] [ka]

[0021] In formulae (P1-A) to (P1-D), "*" represents the bonding position with L1 in formula (1). 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms. The alkyl group may be a straight-chain or branched alkyl group, or an alkyl group having a cyclic structure (cycloalkyl group). The alkyl group preferably has 1 to 5 carbon atoms. The group represented by formula (P1-A) is preferably one unit of a partial structure of a poly(meth)acrylic acid ester obtained by polymerization of a (meth)acrylic acid ester. The group represented by formula (P1-B) is preferably an ethylene glycol unit formed by ring-opening polymerization of the epoxy group of a compound having an epoxy group. The group represented by the formula (P1-C) is preferably a propylene glycol unit formed by ring-opening polymerization of the oxetane group of a compound having an oxetane group. The group represented by formula (P1-D) is preferably a siloxane unit of a polysiloxane obtained by condensation polymerization of a compound having at least one of an alkoxysilyl group and a silanol group. Here, the compound having at least one of an alkoxysilyl group and a silanol group is preferably a compound represented by the formula SiR 4 (OR 5 )2-, wherein R 4 is R in (P1-D) 4 Synonymous with R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms.

[0022] L1 is a single bond or a divalent linking group. The divalent linking group represented by L1 is -C(O)O-, -OC(O)-, -O-, -S-, or -C(O)NR 3 -, -NR 3 C(O)-, -SO2-, and -NR 3 R 4 In the formula, R 3 and R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent. When P1 is a group represented by formula (P1-A), L1 is preferably a group represented by -C(O)O- because the effects of the present invention are better. When P1 is a group represented by any one of the formulae (P1-B) to (P1-D), L1 is preferably a single bond because the effects of the present invention are more excellent.

[0023] The spacer group represented by SP1 preferably contains at least one structure selected from the group consisting of an oxyethylene structure, an oxypropylene structure, a polysiloxane structure, and an alkylene fluoride structure, for reasons such as the ease of expressing liquid crystallinity and the availability of raw materials. Here, the oxyethylene structure represented by SP1 is *-(CH2-CH2O) n1 A group represented by -* is preferred. In the formula, n1 represents an integer of 1 to 20, and * represents the bonding position with L1 or M1 in the above formula (1). Because the effects of the present invention are more excellent, n1 is preferably an integer of 2 to 10, more preferably an integer of 2 to 4, and most preferably 3. In addition, the oxypropylene structure represented by SP1 is preferably *-(CH(CH3)-CH2O) because the effect of the present invention is more excellent. n2 A group represented by -* is preferred, in which n2 represents an integer of 1 to 3, and * represents the bonding position to L1 or M1. In addition, the polysiloxane structure represented by SP1 is *-(Si(CH3)2-O) because the effect of the present invention is more excellent. n3 A group represented by -* is preferred, in which n3 represents an integer of 6 to 10, and * represents the bonding position to L1 or M1. In addition, the fluorinated alkylene structure represented by SP1 is preferably *-(CF2-CF2) because the effect of the present invention is more excellent. n4 A group represented by -* is preferred, in which n4 represents an integer of 6 to 10, and * represents the bonding position to L1 or M1.

[0024] The mesogenic group represented by M1 is a group that represents the main skeleton of the liquid crystal molecule that contributes to the formation of liquid crystal. The liquid crystal molecule exhibits liquid crystallinity, which is an intermediate state (mesophase) between the crystalline state and the isotropic liquid state. There are no particular limitations on the mesogenic group, and reference can be made, for example, to the description in "Flussige Kristalle in Tabellen II" (VEB Deutsche Verlag fur Grundstoff Industrie, Leipzig, published in 1984), particularly pages 7 to 16, and the description in "Liquid Crystal Handbook" edited by the Liquid Crystal Handbook Editorial Committee (Maruzen, published in 2000), particularly chapter 3. As the mesogenic group, for example, at least one group having a cyclic structure selected from the group consisting of an aromatic hydrocarbon group, a heterocyclic group, and an alicyclic group is preferable. The mesogenic group preferably has an aromatic hydrocarbon group, more preferably has 2 to 4 aromatic hydrocarbon groups, and even more preferably has 3 aromatic hydrocarbon groups, because this provides better effects for the present invention.

[0025] As the mesogenic group, from the viewpoints of expression of liquid crystallinity, adjustment of the liquid crystal phase transition temperature, availability of raw materials and suitability for synthesis, as well as because the effects of the present invention are superior, a group represented by the following formula (M1-A) or the following formula (M1-B) is preferred, and a group represented by formula (M1-B) is more preferred.

[0026] [ka]

[0027] In formula (M1-A), A1 is a divalent group selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups. These groups may be substituted with an alkyl group, a fluorinated alkyl group, an alkoxy group, or a substituent. The divalent group represented by A1 is preferably a 4- to 6-membered ring. In addition, the divalent group represented by A1 may be a monocyclic ring or a condensed ring. * indicates the binding position to SP1 or T1.

[0028] Examples of the divalent aromatic hydrocarbon group represented by A1 include a phenylene group, a naphthylene group, a fluorene-diyl group, an anthracene-diyl group, and a tetracene-diyl group. From the viewpoints of the diversity of mesogenic skeleton designs and the availability of raw materials, a phenylene group or a naphthylene group is preferred, and a phenylene group is more preferred.

[0029] The divalent heterocyclic group represented by A1 may be either aromatic or non-aromatic, but is preferably a divalent aromatic heterocyclic group from the viewpoint of further improving the degree of orientation. The atoms other than carbon constituting the divalent aromatic heterocyclic group include a nitrogen atom, a sulfur atom, and an oxygen atom. When the aromatic heterocyclic group has a plurality of atoms other than carbon constituting the ring, these atoms may be the same or different. Specific examples of divalent aromatic heterocyclic groups include, for example, a pyridylene group (pyridine-diyl group), a pyridazine-diyl group, an imidazole-diyl group, a thienylene (thiophene-diyl group), a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), an oxazole-diyl group, a thiazole-diyl group, an oxadiazole-diyl group, a benzothiazole-diyl group, a benzothiadiazole-diyl group, a phthalimido-diyl group, a thienothiazole-diyl group, a thiazolothiazole-diyl group, a thienothiophene-diyl group, and a thienoxazole-diyl group.

[0030] Specific examples of the divalent alicyclic group represented by A1 include a cyclopentylene group and a cyclohexylene group.

[0031] In formula (M1-A), a1 represents an integer of 1 to 10. When a1 is 2 or more, multiple A1 may be the same or different.

[0032] In formula (M1-B), A2 and A3 are each independently a divalent group selected from the group consisting of an aromatic hydrocarbon group, a heterocyclic group, and an alicyclic group. Specific examples and preferred embodiments of A2 and A3 are the same as those of A1 in formula (M1-A), and therefore the description thereof is omitted. In formula (M1-B), a2 represents an integer of 1 to 10, and when a2 is 2 or more, multiple A2 may be the same or different, multiple A3 may be the same or different, and multiple LA1 may be the same or different. For reasons of better effects of the present invention, a2 is preferably an integer of 2 or more, and more preferably 2. In formula (M1-B), when a2 is 1, LA1 is a divalent linking group. When a2 is 2 or more, each of the multiple LA1 is independently a single bond or a divalent linking group, and at least one of the multiple LA1 is a divalent linking group. When a2 is 2, it is preferable that one of the two LA1 is a divalent linking group and the other is a single bond, because the effect of the present invention is more excellent.

[0033] In formula (M1-B), the divalent linking group represented by LA1 is -O-, -(CH2) g -, -(CF2) g -, -Si(CH3)2-, -(Si(CH3)2O) g -, -(OSi(CH3)2) g -(g represents an integer from 1 to 10.), -N(Z)-, -C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)2 -C(Z')2-, -C(O)-, -OC(O)-, -C(O)O-, -OC(O)O-, -N(Z)C(O)-, -C(O)N(Z)- , -C(Z)=C(Z')-C(O)O-, -OC(O)-C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z )=C(Z')-C(O)N(Z”)-, -N(Z”)-C(O)-C(Z)=C(Z')-, -C(Z)=C(Z')-C(O)-S- , -SC(O)-C(Z)=C(Z')-, -C(Z)=NN=C(Z')- (Z, Z', and Z" independently represent hydrogen, a C1 to C4 alkyl group, a cycloalkyl group, an aryl group, a cyano group, or a halogen atom), -C≡C-, -N=N-, -S-, -S(O)-, -S(O)(O)-, -(O)S(O)O-, -O(O)S(O)O-, -SC(O)-, and -C(O)S-. Of these, -C(O)O- is preferred because it provides better effects of the present invention. LA1 may be a group consisting of a combination of two or more of these groups.

[0034] Specific examples of M1 include the following structures: In the following specific examples, "Ac" represents an acetyl group.

[0035] [ka]

[0036] [ka]

[0037] Examples of the terminal group represented by T1 include a hydrogen atom, a halogen atom, a cyano group, a nitro group, a hydroxy group, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, an alkoxycarbonyloxy group having 1 to 10 carbon atoms, an alkoxycarbonyl group having 1 to 10 carbon atoms (ROC(O)-: R is an alkyl group), an acyloxy group having 1 to 10 carbon atoms, an acylamino group having 1 to 10 carbon atoms, an alkoxycarbonylamino group having 1 to 10 carbon atoms, a sulfonylamino group having 1 to 10 carbon atoms, a sulfamoyl group having 1 to 10 carbon atoms, a carbamoyl group having 1 to 10 carbon atoms, a sulfinyl group having 1 to 10 carbon atoms, a ureido group having 1 to 10 carbon atoms, and a (meth)acryloyloxy group-containing group. Examples of the (meth)acryloyloxy group-containing group include a group represented by -LA (L represents a single bond or a linking group. Specific examples of the linking group are the same as those of L1 and SP1 described above. A represents a (meth)acryloyloxy group). T1 is preferably an alkoxy group having 1 to 10 carbon atoms, more preferably an alkoxy group having 1 to 5 carbon atoms, and even more preferably a methoxy group, because the effects of the present invention are more excellent. These terminal groups may be further substituted with these groups or with the polymerizable groups described in JP-A-2010-244038. The number of atoms in the main chain of T1 is preferably 1 to 20, more preferably 1 to 15, further preferably 1 to 10, and particularly preferably 1 to 7, because the effects of the present invention are more excellent. When the number of atoms in the main chain of T1 is 20 or less, the degree of orientation of the polarizer is further improved. Here, the "main chain" in T1 means the longest molecular chain bonded to M1, and hydrogen atoms are not counted in the number of atoms in the main chain of T1. For example, when T1 is an n-butyl group, the number of atoms in the main chain is 4, and when T1 is a sec-butyl group, the number of atoms in the main chain is 3.

[0038] The content of the repeating unit (1) is preferably 20 to 100% by mass based on 100% by mass of all repeating units contained in the polymeric liquid crystal compound, because this provides better effects for the present invention. In the present invention, the content of each repeating unit contained in the polymeric liquid crystal compound is calculated based on the charged amount (mass) of each monomer used to obtain each repeating unit. The repeating unit (1) may be contained in the polymeric liquid crystal compound in one kind or in two or more kinds. In particular, it is preferable that the polymeric liquid crystal compound contains two kinds of repeating units (1) because the effect of the present invention is more excellent.

[0039] When the polymeric liquid crystal compound contains two types of repeating units (1), it is preferable that the terminal group represented by T1 in one (repeating unit A) is an alkoxy group, and the terminal group represented by T1 in the other (repeating unit B) is a group other than an alkoxy group, because this provides a better effect of the present invention. In the repeating unit B, the terminal group represented by T1 is preferably an alkoxycarbonyl group, a cyano group, or a (meth)acryloyloxy group-containing group, and more preferably an alkoxycarbonyl group or a cyano group, because the effects of the present invention are more excellent. The ratio (A / B) of the content of the repeating unit A in the polymeric liquid crystal compound to the content of the repeating unit B in the polymeric liquid crystal compound is preferably 50 / 50 to 95 / 5, more preferably 60 / 40 to 93 / 7, and even more preferably 70 / 30 to 90 / 10, because the effects of the present invention are more excellent.

[0040] (Weight average molecular weight) For reasons of superior effects of the present invention, the weight average molecular weight (Mw) of the polymer liquid crystal compound is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. When the Mw of the polymer liquid crystal compound is within the above range, the polymer liquid crystal compound becomes easy to handle. In particular, from the viewpoint of suppressing cracks during application, the weight average molecular weight (Mw) of the polymeric liquid crystal compound is preferably 10,000 or more, and more preferably 10,000 to 300,000. From the viewpoint of the temperature latitude of the orientation degree, the polymer liquid crystal compound preferably has a weight average molecular weight (Mw) of less than 10,000, and more preferably from 2,000 to less than 10,000. Here, the weight average molecular weight and number average molecular weight in the present invention are values ​​measured by gel permeation chromatography (GPC). Solvent (eluent): N-methylpyrrolidone ·Device name: TOSOH HLC-8220GPC Column: Three TOSOH TSKgel SuperAWM-H (6 mm x 15 cm) columns connected together Column temperature: 25℃ Sample concentration: 0.1% by mass ·Flow rate: 0.35mL / min Calibration curve: TOSOH TSK standard polystyrene Calibration curve using 7 samples with Mw = 2,800,000 to 1,050 (Mw / Mn = 1.03 to 1.06)

[0041] <First dichroic material> The composition contains a first dichroic substance. The first dichroic substance is not particularly limited as long as it can form an array structure with the second dichroic substance, but is preferably a compound having a chromophore that is the core of the dichroic substance and a side chain that is bonded to an end of the chromophore. Specific examples of the chromophore include an aromatic ring group (e.g., an aromatic hydrocarbon group, an aromatic heterocyclic group) and an azo group. A structure having both an aromatic ring group and an azo group is preferred, and a bisazo structure having an aromatic heterocyclic group (preferably a thienothiazole group) and two azo groups is more preferred. The side chain is not particularly limited, and examples thereof include groups represented by R1, R2, or R3 in formula (1) described below.

[0042] From the viewpoint of adjusting the color of the polarizer, the first dichroic material is preferably a dichroic material having a maximum absorption wavelength in the range of 560 nm or more and 700 nm or less (more preferably 560 to 650 nm, particularly preferably 560 to 640 nm). In this specification, the maximum absorption wavelength (nm) of a dichroic substance is determined from an ultraviolet-visible light spectrum in the wavelength range of 380 to 800 nm measured with a spectrophotometer using a solution in which the dichroic substance is dissolved in a good solvent.

[0043] The first dichroic material is preferably a compound represented by formula (1) in that the degree of orientation of the polarizer is further improved.

[0044] [ka]

[0045] In formula (1), Ar1 and Ar2 each independently represent a phenylene group which may have a substituent or a naphthylene group which may have a substituent, with a phenylene group being preferred.

[0046] In formula (1), R1 represents a hydrogen atom, a linear or branched alkyl group having 1 to 20 carbon atoms which may have a substituent, an alkoxy group, an alkylthio group, an alkylsulfonyl group, an alkylcarbonyl group, an alkyloxycarbonyl group, an acyloxy group, an alkylcarbonate group, an alkylamino group, an acylamino group, an alkylcarbonylamino group, an alkoxycarbonylamino group, an alkylsulfonylamino group, an alkylsulfamoyl group, an alkylcarbamoyl group, an alkylsulfinyl group, an alkylureido group, an alkylphosphoric acid amide group, an alkylimino group, or an alkylsilyl group. The carbon atoms of the alkyl group may be optionally substituted by -O-, -CO-, -C(O)-O-, -OC(O)-, -Si(CH3)2-O-Si(CH3)2-, -N(R1')-, -N(R1')-CO-, -CO-N(R1')-, -N(R1')-C(O)-O-, -OC(O)-N(R1')-, -N(R1')-C(O)-N(R1')-, -CH=CH-, -C≡C-, -N=N-, -C(R1')=CH-C(O)- or -OC(O)-O-. When R1 is a group other than a hydrogen atom, the hydrogen atom of each group may be replaced by a halogen atom, a nitro group, a cyano group, -N(R1')2, an amino group, -C(R1')=C(R1')-NO2, -C(R1')=C(R1')-CN, or -C(R1')=C(CN)2. R1' represents a hydrogen atom or a linear or branched alkyl group having a carbon number of 1 to 6. When there are a plurality of R1' in each group, they may be the same or different.

[0047] In formula (1), R2 and R3 each independently represent a hydrogen atom, a linear or branched alkyl group having 1 to 20 carbon atoms which may have a substituent, an alkenyl group, an alkoxy group, an acyl group, an alkyloxycarbonyl group, an alkylamide group, an alkylsulfonyl group, an aryl group, an arylcarbonyl group, an arylsulfonyl group, an aryloxycarbonyl group, or an arylamide group. The carbon atoms of the alkyl group may be optionally substituted by -O-, -S-, -C(O)-, -C(O)-O-, -OC(O)-, -C(O)-S-, -SC(O)-, -Si(CH3)2-O-Si(CH3)2-, -NR2'-, -NR2'-CO-, -CO-NR2'-, -NR2'-C(O)-O-, -OC(O)-NR2'-, -NR2'-C(O)-NR2'-, -CH=CH-, -C≡C-, -N=N-, -C(R2')=CH-C(O)- or -OC(O)-O-. When R2 and R3 are groups other than hydrogen atoms, the hydrogen atoms of each group may be replaced by halogen atoms, nitro groups, cyano groups, -OH groups, -N(R2')2, amino groups, -C(R2')=C(R2')-NO2, -C(R2')=C(R2')-CN, or -C(R2')=C(CN)2. R2' represents a hydrogen atom or a linear or branched alkyl group having a carbon number of 1 to 6. When there are a plurality of R2' in each group, they may be the same or different. R2 and R3 may be bonded to each other to form a ring, or R2 or R3 may be bonded to Ar2 to form a ring.

[0048] From the viewpoint of light resistance, R1 is preferably an electron-withdrawing group, and R2 and R3 are preferably groups having low electron-donating properties. Specific examples of such groups include alkylsulfonyl groups, alkylcarbonyl groups, alkyloxycarbonyl groups, acyloxy groups, alkylsulfonylamino groups, alkylsulfamoyl groups, alkylsulfinyl groups, and alkylureido groups for R1, and groups of the following structure for R2 and R3, which are shown in the above formula (1) including the nitrogen atom to which R2 and R3 are bonded.

[0049] [ka]

[0050] Specific examples of the first dichroic material are shown below, but the present invention is not limited thereto.

[0051] [ka]

[0052] <Second dichroic material> The composition contains a second dichroic material. The second dichroic material is a compound different from the first dichroic material, specifically, the second dichroic material has a different chemical structure. The second dichroic substance is not particularly limited as long as it can form an array structure with the first dichroic substance, but it is preferable that the second dichroic substance is a compound having a chromophore that is the core of the dichroic substance and a side chain that is bonded to an end of the chromophore. Specific examples of the chromophore include aromatic ring groups (e.g., aromatic hydrocarbon groups, aromatic heterocyclic groups) and azo groups. A structure having both an aromatic hydrocarbon group and an azo group is preferred, and a bisazo or trisazo structure having an aromatic hydrocarbon group and two or three azo groups is more preferred. The side chain is not particularly limited, and examples thereof include groups represented by R4, R5, or R6 in formula (2) described below.

[0053] From the viewpoint of adjusting the color of the polarizer, the second dichroic material is preferably a dichroic material having a maximum absorption wavelength in the range of 455 nm or more and less than 560 nm (more preferably 455 to 555 nm, particularly preferably 455 to 550 nm). In particular, by using a first dichroic material having a maximum absorption wavelength of 560 to 700 nm and a second dichroic material having a maximum absorption wavelength of 455 nm or more and less than 560 nm, it becomes easier to adjust the color of the polarizer.

[0054] The second dichroic material is preferably a compound represented by formula (2) in that the degree of orientation of the polarizer is further improved.

[0055] [ka]

[0056] In formula (2), n represents 1 or 2. In formula (2), Ar3, Ar4 and Ar5 each independently represent a phenylene group which may have a substituent, a naphthylene group which may have a substituent, or a heterocyclic group which may have a substituent. The heterocyclic group may be either aromatic or non-aromatic. Examples of the atoms other than carbon that constitute the aromatic heterocyclic group include a nitrogen atom, a sulfur atom, and an oxygen atom. When the aromatic heterocyclic group has a plurality of atoms that constitute the ring other than carbon, these atoms may be the same or different. Specific examples of aromatic heterocyclic groups include, for example, a pyridylene group (pyridine-diyl group), a pyridazine-diyl group, an imidazole-diyl group, a thienylene (thiophene-diyl group), a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), an oxazole-diyl group, a thiazole-diyl group, an oxadiazole-diyl group, a benzothiazole-diyl group, a benzothiadiazole-diyl group, a phthalimido-diyl group, a thienothiazole-diyl group, a thiazolothiazole-diyl group, a thienothiophene-diyl group, and a thienoxazole-diyl group.

[0057] In formula (2), the definition of R4 is the same as that of R1 in formula (1). In formula (2), R5 and R6 are defined the same as R2 and R3 in formula (1), respectively.

[0058] From the viewpoint of light resistance, R4 is preferably an electron-withdrawing group, and R5 and R6 are preferably groups having low electron-donating properties. Among such groups, specific examples when R4 is an electron-withdrawing group are the same as the specific examples when R1 is an electron-withdrawing group, and specific examples when R5 and R6 are groups with low electron-donating property are the same as the specific examples when R2 and R3 are groups with low electron-donating property.

[0059] Specific examples of the second dichroic material are shown below, but the present invention is not limited thereto.

[0060] [ka]

[0061] (difference in logP values) The absolute value of the difference between the logP value of the side chain of the first dichroic material and the logP value of the side chain of the second dichroic material (hereinafter also referred to as "logP difference") is preferably 2.30 or less, more preferably 2.0 or less, even more preferably 1.5 or less, and particularly preferably 1.0 or less. If the logP difference is 2.30 or less, the affinity between the first dichroic material and the second dichroic material is increased, making it easier to form an aligned structure, and thus the degree of orientation of the polarizer is further improved. When the first dichroic substance or the second dichroic substance has a plurality of side chains, it is preferable that at least one of the logP differences satisfies the above value. Here, the side chains of the first dichroic material and the second dichroic dye refer to groups bonded to the ends of the above-mentioned chromophores. For example, when the first dichroic material is a compound represented by formula (1), R1, R2, and R3 in formula (1) are side chains, and when the second dichroic material is a compound represented by formula (2), R4, R5, and R6 in formula (2) are side chains. In particular, when the first dichroic material is a compound represented by formula (1) and the second dichroic material is a compound represented by formula (2), it is preferable that at least one of the logP differences between R1 and R4, the logP difference between R1 and R5, the logP difference between R2 and R4, and the logP difference between R2 and R5 satisfies the above value.

[0062] Here, the logP value is an index expressing the hydrophilic and hydrophobic properties of a chemical structure, and is sometimes called the hydrophilic-hydrophobic parameter. The logP value can be calculated using software such as ChemBioDraw Ultra or HSPiP (Ver. 4.1.07). It can also be experimentally determined by the method of OECD Guidelines for the Testing of Chemicals, Section 1, Test No. 117, etc. In the present invention, unless otherwise specified, the value calculated by inputting the structural formula of a compound into HSPiP (Ver. 4.1.07) is adopted as the logP value.

[0063] <Third dichroic material> The composition preferably contains a third dichroic material. The third dichroic material is a dichroic material other than the first dichroic material and the second dichroic material, and specifically, has a different chemical structure from the first dichroic material and the second dichroic material. If the composition contains a third dichroic material, there is an advantage that the color of the polarizer can be easily adjusted. The maximum absorption wavelength of the third dichroic substance is preferably 380 nm or more and less than 455 nm, and more preferably 385 to 454 nm. Specific examples of the third dichroic substance include compounds represented by formula (1) described in WO 2017 / 195833, other than the first dichroic substance and the second dichroic substance.

[0064] (Dichroic substance content) In the present composition, the content of the dichroic substance is preferably 0.1 to 99 parts by mass, more preferably 1 to 60 parts by mass, and particularly preferably 1.5 to 30 parts by mass, per 100 parts by mass of the total amount of the dichroic substance and the liquid crystal compound. The content of the first dichroic substance is preferably 40 to 90 parts by mass, and more preferably 55 to 85 parts by mass, based on 100 parts by mass of the dichroic substance content in the composition. The content of the second dichroic substance is preferably 6 to 50 parts by mass, and more preferably 8 to 45 parts by mass, based on 100 parts by mass of the dichroic substance contained in the composition. When the present composition contains a third dichroic substance, the content of the third dichroic substance is preferably 3 to 30 parts by mass, and more preferably 5 to 25 parts by mass, per 100 parts by mass of the dichroic substance content in the present composition. The content of dichroic substances means the total amount of the first dichroic substance and the second dichroic substance, and if the composition contains a third dichroic substance, the content of the third dichroic substance is also included in the total amount. The content ratio of the first dichroic material, the second dichroic material, and the third dichroic material used as necessary can be set arbitrarily in order to adjust the color of the polarizer. However, the content ratio of the second dichroic material to the first dichroic material (second dichroic material / first dichroic material) is preferably 0.1 to 10, more preferably 0.2 to 5, and particularly preferably 0.3 to 0.8, in terms of moles. When the content ratio of the second dichroic material to the first dichroic material is within the above range, the first dichroic material and the second dichroic material are more likely to form an array structure.

[0065] <Solvent> From the viewpoint of workability and the like, the present composition preferably contains a solvent. Examples of the solvent include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone), ethers (e.g., dioxane, tetrahydrofuran, tetrahydropyran, dioxolane, tetrahydrofurfuryl alcohol, and cyclopentyl methyl ether), aliphatic hydrocarbons (e.g., hexane), alicyclic hydrocarbons (e.g., cyclohexane), aromatic hydrocarbons (e.g., benzene, toluene, xylene, and trimethylbenzene), halogenated carbons (e.g., dichloromethane, trichloromethane (chloroform), dichloroethane, dichlorobenzene, and chlorotoluene), and the like. Examples of the organic solvent include organic solvents such as ethanol, esters (e.g., methyl acetate, ethyl acetate, butyl acetate, diethyl carbonate, etc.), alcohols (e.g., ethanol, isopropanol, butanol, cyclohexanol, etc.), cellosolves (e.g., methyl cellosolve, ethyl cellosolve, 1,2-dimethoxyethane, etc.), cellosolve acetates, sulfoxides (e.g., dimethyl sulfoxide, etc.), amides (e.g., dimethylformamide, dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, etc.), and heterocyclic compounds (e.g., pyridine, etc.), as well as water. These solvents may be used alone or in combination of two or more. Of these solvents, it is preferable to use an organic solvent, and it is more preferable to use a halogenated carbon or a ketone, because the effects of the present invention are more excellent. When the composition contains a solvent, the content of the solvent is preferably 70 to 99.5 mass%, more preferably 80 to 99 mass%, and even more preferably 85 to 98 mass%, relative to the total mass of the composition, because this provides better effects of the present invention.

[0066] <Interfacial improver> The present composition preferably contains an interface improver, which is expected to improve the smoothness of the coating surface, improve the degree of orientation, and suppress repelling and unevenness, thereby improving the in-plane uniformity. The interface improver is preferably one that horizontally aligns the liquid crystal compound, and the compounds (horizontal alignment agents) described in paragraphs

[0253] to

[0293] of JP-A-2011-237513 can be used. In addition, fluorine (meth)acrylate-based polymers described in paragraphs

[0018] to

[0043] of JP-A-2007-272185 can also be used. Compounds other than these may also be used as the interface improver. When the present composition contains an interface modifier, the content of the interface modifier is preferably 0.001 to 5 parts by mass, and more preferably 0.01 to 3 parts by mass, per 100 parts by mass of the total of the liquid crystal compound and the dichroic substance in the present composition, because this provides better effects of the present invention.

[0067] <Polymerization initiator> The present composition preferably contains a polymerization initiator because the effects of the present invention are more excellent. The polymerization initiator is not particularly limited, but is preferably a compound having photosensitivity, that is, a photopolymerization initiator. As the photopolymerization initiator, various compounds can be used without any particular limitation. Examples of the photopolymerization initiator include α-carbonyl compounds (U.S. Pat. Nos. 2,367,661 and 2,367,670), acyloin ethers (U.S. Pat. No. 2,448,828), α-hydrocarbon-substituted aromatic acyloin compounds (U.S. Pat. No. 2,722,512), polynuclear quinone compounds (U.S. Pat. Nos. 3,046,127 and 2,951,758), and combinations of triaryl imidazole dimers and p-aminophenyl ketones. Examples of such compounds include compounds (U.S. Pat. No. 3,549,367), acridine and phenazine compounds (Japanese Patent Laid-Open No. 60-105667 and U.S. Pat. No. 4,239,850), oxadiazole compounds (U.S. Pat. No. 4,212,970), and acylphosphine oxide compounds (Japanese Patent Publication No. 63-40799, Japanese Patent Publication No. 5-29234, Japanese Patent Laid-Open No. 10-95788 and Japanese Patent Laid-Open No. 10-29997). As such a photopolymerization initiator, commercially available products can be used, such as Irgacure 184, Irgacure 907, Irgacure 369, Irgacure 651, Irgacure 819, and Irgacure OXE-01 manufactured by BASF. When the composition contains a polymerization initiator, the content of the polymerization initiator is preferably 0.01 to 30 parts by mass, and more preferably 0.1 to 15 parts by mass, relative to 100 parts by mass of the total of the liquid crystal compound and the dichroic substance in the composition, because the effects of the present invention are more excellent. If the content of the polymerization initiator is 0.01 part by mass or more, the durability of the polarizer becomes good, and if it is 30 parts by mass or less, the alignment of the polarizer becomes better.

[0068] <Substituent> The substituents in this specification will be described. Examples of the substituent include an alkyl group (preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 12 carbon atoms, and particularly preferably an alkyl group having 1 to 8 carbon atoms, such as a methyl group, an ethyl group, an isopropyl group, a tert-butyl group, an n-octyl group, an n-decyl group, an n-hexadecyl group, a cyclopropyl group, a cyclopentyl group, and a cyclohexyl group), an alkenyl group (preferably an alkenyl group having 2 to 20 carbon atoms, more preferably an alkenyl group having 2 to 12 carbon atoms, and particularly preferably an alkenyl group having 2 to 8 carbon atoms, such as a vinyl group, an aryl group, and a 2-butenyl group). groups, and 3-pentenyl groups, etc.), alkynyl groups (preferably alkynyl groups having 2 to 20 carbon atoms, more preferably 2 to 12 carbon atoms, and particularly preferably 2 to 8 carbon atoms, such as a propargyl group and a 3-pentenyl group, etc.), aryl groups (preferably aryl groups having 6 to 30 carbon atoms, more preferably 6 to 20 carbon atoms, and particularly preferably 6 to 12 carbon atoms, such as a phenyl group, a 2,6-diethylphenyl group, a 3,5-ditrifluoromethylphenyl group, a styryl group, a naphthyl group, and a biphenyl group, etc. a substituted or unsubstituted amino group (preferably having 0 to 20 carbon atoms, more preferably having 0 to 10 carbon atoms, and particularly preferably having 0 to 6 carbon atoms; examples of which include an unsubstituted amino group, a methylamino group, a dimethylamino group, a diethylamino group, and an anilino group), an alkoxy group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 15 carbon atoms, and examples of which include a methoxy group, an ethoxy group, and a butoxy group), an oxycarbonyl group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 15 carbon atoms, and particularly preferably having 2 to 6 carbon atoms). 10, for example, a methoxycarbonyl group, an ethoxycarbonyl group, a phenoxycarbonyl group, etc.), an acyloxy group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 10 carbon atoms, particularly preferably having 2 to 6 carbon atoms, for example, an acetoxy group, a benzoyloxy group, an acryloyl group, etc.), an acylamino group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 10 carbon atoms, particularly preferably having 2 to 6 carbon atoms, for example, an acetylamino group, a benzoylamino group, etc.),Examples of such groups include an alkoxycarbonylamino group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 10 carbon atoms, and particularly preferably having 2 to 6 carbon atoms; for example, a methoxycarbonylamino group), an aryloxycarbonylamino group (preferably having 7 to 20 carbon atoms, more preferably having 7 to 16 carbon atoms, and particularly preferably having 7 to 12 carbon atoms; for example, a phenyloxycarbonylamino group), a sulfonylamino group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; for example, a methanesulfonylamin a benzenesulfonylamino group, and the like), a sulfamoyl group (preferably having 0 to 20 carbon atoms, more preferably having 0 to 10 carbon atoms, and particularly preferably having 0 to 6 carbon atoms, and examples thereof include a sulfamoyl group, a methylsulfamoyl group, a dimethylsulfamoyl group, and a phenylsulfamoyl group), a carbamoyl group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms, and examples thereof include an unsubstituted carbamoyl group, a methylcarbamoyl group, a diethylcarbamoyl group, and a phenylcarbamoyl group). bamoyl group, etc.), alkylthio group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples of which include a methylthio group and an ethylthio group), arylthio group (preferably having 6 to 20 carbon atoms, more preferably having 6 to 16 carbon atoms, and particularly preferably having 6 to 12 carbon atoms; examples of which include a phenylthio group, etc.), sulfonyl group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples of which include a mesyl group and a tosyl group, etc. a sulfinyl group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples of which include a methanesulfinyl group and a benzenesulfinyl group), a ureido group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples of which include an unsubstituted ureido group, a methylureido group, and a phenylureido group), a phosphoric acid amide group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and particularly preferably having 1 to 6 carbon atoms; examples of which includediethylphosphoramide group, and phenylphosphoramide group), a hydroxy group, a mercapto group, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom), a cyano group, a nitro group, a hydroxamic acid group, a sulfino group, a hydrazino group, an imino group, an azo group, a heterocyclic group (preferably a heterocyclic group having 1 to 30 carbon atoms, more preferably a heterocyclic group having 1 to 12 carbon atoms, for example, a heterocyclic group having a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom, for example, an epoxy group, an oxy group, Examples of the silyl group include cetanyl group, imidazolyl group, pyridyl group, quinolyl group, furyl group, piperidyl group, morpholino group, maleimide group, benzoxazolyl group, benzimidazolyl group, and benzthiazolyl group), silyl group (preferably a silyl group having 3 to 40 carbon atoms, more preferably a silyl group having 3 to 30 carbon atoms, and particularly preferably a silyl group having 3 to 24 carbon atoms, and examples thereof include a trimethylsilyl group and a triphenylsilyl group), a carboxy group, a sulfonic acid group, and a phosphate group.

[0069] [Aggregates in polarizers] In the arrangement structure formed from the first dichroic material and the second dichroic material in the present invention, the first dichroic material and the second dichroic material preferably form an association, which has the advantages of further improving the degree of orientation and light resistance of the polarizer and facilitating color adjustment of the polarizer.

[0070] A method for verifying that the first dichroic substance and the second dichroic substance have formed an aggregate can be based on the maximum absorption wavelength measured using a film formed as follows. In producing each film (polarizer), care is taken to ensure that the type of the lower layer (e.g., substrate), the concentration of the composition, and the application conditions are the same, and that the area and thickness of the films are the same, except for changing the type of dichroic material contained in each film.

[0071] Specifically, the composition (a composition containing at least a first dichroic material, a second dichroic material, and a liquid crystal compound) is cast onto a substrate (e.g., soda lime glass), the composition is heated on a hot plate until it becomes liquid crystal, and then cooled to room temperature to form a film 1 (corresponding to the polarizer of the present invention). Then, the absorption spectrum of the film 1 is measured at 1 nm intervals in a wavelength range of 380 to 800 nm. The film 1 is heated again every 10°C to measure the absorption spectrum, and the maximum absorption wavelength λ1 is determined. In addition, a composition 4 (a composition that does not contain a second dichroic material and contains at least a liquid crystal compound and a first dichroic material) containing the same components as the present composition except that it does not contain a second dichroic material is prepared. Then, the absorption spectrum of a film 1-4 formed using the composition 4 is obtained in the same manner as in the measurement of the absorption spectrum of the film 1 (the polarizer of the present invention). Then, the absorption spectrum of film 1-4 is subtracted from the absorption spectrum of film 1 to obtain a difference spectrum, and the maximum absorption wavelength λ of the obtained difference spectrum is determined.

[0072] Next, a composition 2 (a composition that does not contain the first dichroic material and contains at least a liquid crystal compound and a second dichroic material) having the same composition as this composition except that it does not contain the first dichroic material is prepared. Then, the maximum absorption wavelength λ2 of a film 1-2 formed using the composition 2 is obtained in the same manner as the measurement of the maximum absorption wavelength λ1 of the film 1 (the polarizer of the present invention).

[0073] FIG. 3 is a diagram showing the absorption spectrum of each film prepared as described above. As shown in FIG. 3, in the polarizer of the present invention, the maximum absorption wavelength λ and the maximum absorption wavelength λ2 are preferably different. Here, in the present invention, "the maximum absorption wavelength λ and the maximum absorption wavelength λ2 are different" means that the absolute value of the difference between the maximum absorption wavelength λ and the maximum absorption wavelength λ2 is greater than 2 nm. In addition, the absolute value of the difference between the maximum absorption wavelength λ and the maximum absorption wavelength λ2 is preferably 5 nm or more, more preferably 10 nm or more. The upper limit of the absolute value of the difference between the maximum absorption wavelength λ and the maximum absorption wavelength λ2 is preferably 100 nm or less. In this way, if the maximum absorption wavelength λ and the maximum absorption wavelength λ2 are different, it can be said that the first dichroic substance and the second dichroic substance are associated with each other. The reason for this will be explained below. The difference in composition between Film 1 and Film 1-4 is the presence or absence of the second dichroic material. Therefore, it is expected that the difference spectrum between the absorption spectrum of Film 1 and the absorption spectrum of Film 1-4 will almost coincide with the absorption spectrum derived from the second dichroic material. Therefore, when the maximum absorption wavelength λ of the difference spectrum coincides with the maximum absorption wavelength λ2 of the absorption spectrum of Film 2 (containing the second dichroic material but not the first dichroic material), it can be said that the second dichroic material is present in the film (polarizer) without being incorporated into the first dichroic material. In contrast, as shown in Fig. 3, the maximum absorption wavelength λ and the maximum absorption wavelength λ2 are different, which means that the absorption spectrum derived from the second dichroic substance is hardly detected in the difference spectrum. In other words, it is considered that the first dichroic substance and the second dichroic substance are associated in the film 1 (for example, a phenomenon occurs in which one dichroic substance is taken up by the other dichroic substance), and the absorption spectrum of the second dichroic substance is no longer detected in the difference spectrum. In this case, the waveform of the absorption spectrum of the film 1 and the waveform of the absorption spectrum of the film 2 are different.

[0074] As shown in Fig. 3, in the polarizer of the present invention, the maximum absorption wavelength λ1 and the maximum absorption wavelength λ4 are preferably different. Here, in the present invention, "the maximum absorption wavelength λ1 and the maximum absorption wavelength λ4 are different" means that the absolute value of the difference between the maximum absorption wavelength λ1 and the maximum absorption wavelength λ4 is greater than 2 nm. Moreover, the absolute value of the difference between the maximum absorption wavelength λ1 and the maximum absorption wavelength λ4 is preferably 5 nm or more, more preferably 7 nm or more. The upper limit of the absolute value of the difference between the maximum absorption wavelength λ1 and the maximum absorption wavelength λ4 is preferably 40 nm or less. In particular, when the maximum absorption wavelength of the first dichroic material is greater than that of the second dichroic material, it is preferable that the maximum absorption wavelength λ1 is smaller than the maximum absorption wavelength λ4. That is, the value obtained by subtracting λ1 from λ4 (λ4-λ1) is preferably greater than 2 nm, and more preferably 5 nm or greater. The upper limit of the value obtained by subtracting λ1 from λ4 is preferably 40 nm or less. In this way, if the maximum absorption wavelength λ1 and the maximum absorption wavelength λ4 are different, it can be said that the first dichroic substance and the second dichroic substance are associated with each other. The reason for this will be explained below. The difference in composition between Film 1 and Film 1-4 is the presence or absence of a second dichroic material. When the maximum absorption wavelength of the first dichroic material is greater than that of the second dichroic material, the maximum absorption wavelength of the first dichroic material is detected, and it is predicted that the maximum absorption wavelength λ1 of Film 1 and the maximum absorption wavelength λ4 of Film 1-4 will match. Therefore, when the maximum absorption wavelength λ1 and the maximum absorption wavelength λ4 match, it can be said that the first dichroic material is present in the film (polarizer) without being incorporated into the second dichroic material. In contrast, the fact that the maximum absorption wavelength λ1 is smaller than the maximum absorption wavelength λ4 as shown in Fig. 3 means that the absorption spectrum originating from the first dichroic material is weakened. In other words, it is considered that the first dichroic material and the second dichroic material are associated in the film 1 (for example, a phenomenon occurs in which one dichroic material is taken up by the other dichroic material), and the maximum absorption wavelength is shifted to the smaller wavelength side of the maximum absorption wavelength of the second dichroic material.

[0075] [Crystal structure in polarizer] In the arrangement structure formed by the first dichroic material and the second dichroic material in the present invention, the first dichroic material and the second dichroic material preferably form a crystalline structure, which has the advantages of further improving the degree of orientation and light resistance of the polarizer and facilitating color adjustment of the polarizer. The first dichroic substance and the second dichroic substance may form an association and a crystal structure.

[0076] As a method for verifying that the first dichroic material and the second dichroic material form a crystal structure, for example, a method using X-ray diffraction (XRD) method can be mentioned. When the dichroic material forms a crystal structure, a peak corresponding to the crystal structure is observed by X-ray diffraction. In the polarizer of the present invention, in addition to the crystal structure of the first dichroic material and the second dichroic material, a crystal structure of the first dichroic material and a crystal structure of the second dichroic material may be observed. These crystallinities can be observed by the intensity of the X-ray peaks derived from each crystal structure. Specifically, when a first dichroic substance and a second dichroic substance are contained and a crystal structure is formed by the first dichroic substance and the second dichroic substance, the peak intensity (P OM ), and the peak intensity due to the crystal structure of the first dichroic material (P M ), and the peak intensity due to the crystal structure of the second dichroic material (P O It is possible that there exists a In addition, the intensity of the peak derived from the crystal structure of the first dichroic substance in the case where the first dichroic substance is contained but the second dichroic substance is not contained (P M1 ), and the peak intensity (P O1 ) is possible. When the first dichroic material and the second dichroic material form a crystal structure, P M and P M1 Unlike P O and P O1 It is different from. M P M1 If P O P O1 If it is smaller than M Peak and P O The peak of P may not be detected. M P M1 and P O P O1If it is greater than M1 Peak and P O1 The peak of P may not be detected. O P O1 When the difference is small relative to the first dichroic substance, this is considered to mean that the crystallinity of the crystal structure derived from the second dichroic substance is reduced (a reduction in the size or number of the crystal structure).

[0077] As a method for verifying whether the first dichroic material and the second dichroic material form a crystal structure, an example of a method using an X-ray diffraction (XRD) method will be described in more detail below. First, a film 1 (the polarizer of the present invention) and a film 1-2 used in measuring the maximum absorption wavelength are prepared. In addition, a composition 3 (a composition that does not contain the first dichroic material and the second dichroic material and contains at least a liquid crystal compound) containing the same components as the composition is prepared, except that the composition does not contain the first dichroic material and the second dichroic material. A film 1-3 is obtained in the same manner as in the production method of the film 1 (the polarizer of the present invention), except that the prepared composition 3 is used. Then, for the film 1 (polarizer of the present invention), film 1-2, and film 3, X-ray diffraction is measured using an X-ray diffraction apparatus for thin film evaluation (manufactured by Rigaku Corporation, product name: "SmartLab" in-plane optical system). Hereinafter, X-ray diffraction analysis performed using the in-plane method is also referred to as "in-plane XRD". In-plane XRD is performed by irradiating the polarizer surface with X-rays using a thin film X-ray diffraction apparatus under the following conditions. Then, the direction in which the liquid crystal and dichroic material are oriented in the long axis direction is set as an azimuth angle (φ) of 0°, and in-plane XRD is performed in all directions at 15° intervals, and the direction in the substrate plane where the peak intensity is maximum is determined by φ scanning performed on the observed peak. The spectrum of the in-plane measurement in the obtained direction is used to compare with the XRD spectrum described later. For the peak intensity, a value normalized as the film thickness equivalent to the X-ray penetration length at an X-ray incidence angle of 0.2° is used.

[0078] Since Film 1, Film 1-2 and Film 1-3 contain a liquid crystal compound, a peak (Peak A) with a half-width of less than 2° (a peak derived from crystals) and a peak (halo) with a half-width of 2° or more (a peak derived from liquid crystals) (Peak B) are observed in the XRD spectrum measured as described above. The diffraction angle of peak A is preferably less than 17° because the effect of the present invention is more excellent. Moreover, the diffraction angle of peak B is preferably 17° or more because the effect of the present invention is more excellent.

[0079] When comparing the XRD spectra of Film 1, Film 1-2, Film 1-3, and Film 1-4, if the following condition (i) or (ii) is satisfied, it is determined that the first dichroic material and the second dichroic material form a crystal structure. Conversely, if neither the following condition (i) nor (ii) is satisfied, it is determined that the first dichroic material and the second dichroic material do not form a crystal structure. Condition (i): Among peaks A of film 1-2, a peak (also called peak O2) having a diffraction angle that is not observed in the XRD spectrum of film 1-3 is not observed in the XRD spectrum of film 1, or even if it is observed in the XRD spectrum of film 1, the peak intensity is greater than that of a peak (also called peak O1) having the same diffraction angle as peak O2. In other words, the ratio of the intensity of peak O1 to the intensity of peak O2 is less than 1. Condition (ii): Among the peaks A of the film 1, a peak (also called peak OM) having a diffraction angle not observed in the XRD spectrum of the film 1-3 is not observed in the XRD spectrum of the film 1-2 and the film 1-4. In other words, if the peak A of the film 1-2 having a diffraction angle not observed in the XRD spectrum of the film 1-3 is called peak O2, and the peak A of the film 1-4 having a diffraction angle not observed in the XRD spectrum of the film 1-3 is called peak M2, the positions of the diffraction angles at which the peaks O2 and M2 are detected are different from the diffraction angle at which the peak OM is detected.

[0080] As described above, the preparation conditions and XRD measurement conditions for films 1, 1-2, 1-3 and 1-4 were the same, so that the peaks of the XRD spectra can be compared.

[0081] First, the reason why it can be determined that the first dichroic material and the second dichroic material form a crystal structure when condition (i) is satisfied will be explained. Peak O2 corresponds to the second dichroic material. Therefore, it is generally considered that peak O2 (peak O1) is also detected in the film 1 (polarizer of the present invention) containing the second dichroic material. In contrast, the phenomenon in which peak O1 is not detected or the intensity of peak O1 is small even though the polarizer contains a second dichroic material is presumably caused by some kind of interaction between the second dichroic material and the first dichroic material in the polarizer, forming a structure (more specifically, a crystal structure) in which the first dichroic material and the second dichroic material are periodically arranged.

[0082] Condition (i) will be specifically described using XRD spectra. Details of the compositions used to form each film will be described in detail in the description of the XRD spectra in Example 1 below. FIG. 4 shows an XRD spectrum of the film 1-2 in which a polymer liquid crystal compound L1 described below is used as the liquid crystal compound and a second dichroic material O1 is used as the second dichroic material. FIG. 5 shows an XRD spectrum of a film (film 1-3) containing only the polymeric liquid crystal compound L1. FIG. 6 shows the XRD spectrum of film 1 (corresponding to polarizer 1 in Example 1 described below) using polymer liquid crystalline compound L1, first dichroic substance M1 described below as the first dichroic substance, and second dichroic substance O1. As can be seen from a comparison of Figures 4 to 6, among the XRD peaks of film 1-2 in Figure 4, peak O2 at a diffraction angle not observed in the XRD of film 1-3 in Figure 5 is not observed in the XRD spectrum of film 1 in Figure 6. Therefore, it is determined that the above-mentioned condition (i) is satisfied, and the first dichroic material and the second dichroic material form a crystal structure.

[0083] Next, the reason why it can be determined that the first dichroic material and the second dichroic material form a crystal structure when condition (ii) is satisfied will be explained. Peak O2 corresponds to the second dichroic material, and peak M2 corresponds to the first dichroic material. Therefore, for film 1 (the polarizer of the present invention) containing the first dichroic material and the second dichroic material, it is considered that only peak O2 and peak M2 are detected as peaks derived from the dichroic materials. In contrast, the phenomenon in which peak OM, which is not observed in the XRD spectra of films 1-2 and 1-4, is detected in film 1 is presumably due to some interaction between the second dichroic material and the first dichroic material in the polarizer, forming a structure (more specifically, a crystal structure) in which the first dichroic material and the second dichroic material are periodically arranged.

[0084] Next, condition (ii) will be specifically explained using XRD spectrum.Note that the following film 2, film 2-2, film 2-3 and film 2-4 correspond to the above-mentioned film 1, film 1-2, film 1-3 and film 1-4, respectively.Note that the details of the composition used to form each film will be described in detail in the description of the XRD spectrum of Example 2 below. FIG. 7 shows an XRD spectrum of a film 2-4 using a polymer liquid crystal compound L1 as a liquid crystal compound and a first dichroic substance M1, which will be described later. FIG. 8 shows an XRD spectrum of a film 2-2 in which a polymer liquid crystal compound L1 described below is used as the liquid crystal compound and a twelfth dichroic material O1 is used as the second dichroic material. FIG. 9 shows an XRD spectrum of the film 2-3 of the polymer liquid crystal compound L1 alone. FIG. 10 shows an XRD spectrum of a film 2 using a polymer liquid crystal compound L1, a first dichroic material M1 as a first dichroic material, and a second dichroic material O1, which will be described later. As can be seen from a comparison of Figures 7, 8, 9, and 10, among the peaks in the XRD spectrum of film 2 in Figure 10, peaks at diffraction angles not observed in the XRD spectra of Figures 7, 8, and 9 are observed in the XRD spectrum of film 2 in Figure 10. Therefore, it is determined that the above-mentioned condition (ii) is satisfied, and the first dichroic material and the second dichroic material form a crystal structure.

[0085] In the present invention, the formation of a crystal structure in the polarizer can be confirmed, for example, by observing the surface or cross section of the polarizer using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). The size of the crystal structure is preferably 1 μm to 500 μm, more preferably 3 μm to 400 μm.

[0086] [Stabilization energy] In order for the first dichroic material and the second dichroic material to form a crystal structure, it is preferable that the theoretically calculated stabilization energy has a certain value. The stabilization energy means the energy loss (energy difference) when one of the first dichroic material and the second dichroic material enters into a structure in which the other dichroic material is arranged alone. Therefore, it is considered that the smaller the value, the smaller the loss, and therefore the easier it is for the other dichroic material to enter, and therefore the easier it is for an arranged structure to be formed. As an example of a method for calculating such stabilization energy, the following method can be given.

[0087] The stabilization energy can be calculated using a commercially available calculation software capable of molecular force field calculations, such as AMBER11. More specifically, using crystal structure information of one dichroic substance (hereinafter also referred to as "dichroic substance A") obtained by a crystal structure analysis method such as XRD, the stabilization energy is calculated based on a structure optimization calculation as the energy when one molecule is replaced with the other dichroic substance (hereinafter also referred to as "dichroic substance B") from a supercell containing multiple unit cells. Here, the supercell is a cell that includes dichroic substance A present within a range of 10 Å or more from the center of gravity of one molecule of dichroic substance A present at the replacement position, starting from the center of gravity of the molecule. The calculation conditions used are force field information called General AMBER Force Field (GAFF) and charge information called Restrained Electro Static Potential (RESP). Here, GAFF can be set using software such as AmberTools included in AMBER11, and RESP can be set by calculating one molecule of each dichroic substance under the HF / 6-31G(d) condition using commercially available software such as Gaussian09, and loading the results into AmberTools. Specifically, the stabilization energy is calculated as the sum X1 of "the energy of a supercell composed only of dichroic substance A before it is replaced with one molecule of dichroic substance B" and "the energy of one molecule of dichroic substance B" obtained using the above calculation conditions, minus the sum X2 of "the energy of a supercell composed only of dichroic substance A before it is replaced with one molecule of dichroic substance B" and "the energy of one molecule of dichroic substance B". The stabilization energy (X1-X2) calculated by the above method is preferably less than 72 kcal / mol, more preferably 55 kcal / mol or less, and more preferably 35 kcal / mol or less, because the alignment structure of the first dichroic material and the second dichroic material is easily formed and a polarizer with a higher degree of alignment can be obtained. The lower limit of the stabilization energy is preferably -13 kcal / mol or more. The ratio (X1 / X2) of the sum X1 to the sum X2 (hereinafter also referred to as "stabilization energy ratio") is preferably 0.22 or more, more preferably 0.40 or more, and particularly preferably 0.60 or more, since an arrangement structure of the first dichroic material and the second dichroic material is easily formed and a polarizer with a higher degree of orientation can be obtained. The upper limit of the stabilization energy ratio is not particularly limited, but is usually 1.50 or less, and preferably 1.30 or less.

[0088] [Method of manufacturing polarizer] Although the method for producing the polarizer of the present invention is not particularly limited, a method (hereinafter also referred to as "the present production method") that includes, in this order, a step of forming a coating film by applying the above-mentioned present composition on an alignment film (hereinafter also referred to as "coating film forming step") and a step of orienting the dichroic material contained in the coating film (hereinafter also referred to as "orientation step") is preferred because it results in a higher degree of orientation of the resulting polarizer. Note that hereinafter, "a higher degree of orientation of the resulting polarizer" is also referred to as "the effect of the present invention is better." Each step will be described below.

[0089] <Coating film formation process> The coating film forming step is a step of forming a coating film by applying the above-mentioned present composition on an alignment film. The liquid crystal compound in the coating film is horizontally aligned due to the interaction between the alignment film and the interfacial modifier (if the present composition contains an interfacial modifier). By using the present composition containing the above-mentioned solvent, or by using the present composition in a liquid state such as a molten liquid by heating or the like, it becomes easy to apply the present composition onto the alignment film. Methods for applying the present composition include known methods such as roll coating, gravure printing, spin coating, wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spraying, and ink jet methods.

[0090] (Alignment film) The alignment film may be any film that can horizontally align the liquid crystal compound contained in the composition. It can be provided by such means as rubbing an organic compound (preferably a polymer) on the film surface, oblique deposition of an inorganic compound, formation of a layer having microgrooves, or accumulation of an organic compound (e.g., ω-tricosanoic acid, dioctadecylmethylammonium chloride, methyl stearate) by the Langmuir-Blodgett method (LB film). Furthermore, alignment films that generate an alignment function by application of an electric field, application of a magnetic field, or irradiation with light are also known. Among these, in the present invention, an alignment film formed by a rubbing process is preferred from the viewpoint of ease of control of the pretilt angle of the alignment film, and a photo-alignment film formed by irradiation with light is also preferred from the viewpoint of uniformity of alignment.

[0091] (1) Rubbed alignment film Polymer materials used for the alignment film formed by rubbing treatment are described in many documents, and many commercial products are available. In the present invention, polyvinyl alcohol or polyimide and derivatives thereof are preferably used. For the alignment film, reference can be made to the description on page 43, line 24 to page 49, line 8 of International Publication No. 2001 / 88574A1. The thickness of the alignment film is preferably 0.01 to 10 μm, and more preferably 0.01 to 1 μm.

[0092] (2) Photo-alignment film Photo-alignment materials used in the alignment film formed by light irradiation are described in many documents. In the present invention, for example, azo compounds described in JP-A-2006-285197, JP-A-2007-76839, JP-A-2007-138138, JP-A-2007-94071, JP-A-2007-121721, JP-A-2007-140465, JP-A-2007-156439, JP-A-2007-133184, JP-A-2009-109831, Japanese Patent No. 3883848, and Japanese Patent No. 4151746, and compounds described in JP-A-2002-229039 are used. Preferred examples include aromatic ester compounds of the above, maleimide and / or alkenyl-substituted nadimide compounds having photo-orientable units described in JP-A-2002-265541 and JP-A-2002-317013, photo-crosslinkable silane derivatives described in JP-A-2002-2205195 and JP-A-2002-2205198, and photo-crosslinkable polyimides, polyamides, or esters described in JP-A-2003-520878, JP-A-2004-529220, or JP-A-2004-22050. More preferred are azo compounds, photo-crosslinkable polyimides, polyamides, or esters.

[0093] A photo-alignment film formed from the above-mentioned material is irradiated with linearly polarized or non-polarized light to produce a photo-alignment film. In this specification, "irradiation with linearly polarized light" and "irradiation with non-polarized light" are operations for causing a photoreaction in a photoalignment material. The wavelength of the light used varies depending on the photoalignment material used, and is not particularly limited as long as it is a wavelength necessary for the photoreaction. The peak wavelength of the light used for photoirradiation is preferably 200 nm to 700 nm, and more preferably ultraviolet light with a peak wavelength of 400 nm or less.

[0094] Examples of light sources used for light irradiation include commonly used light sources, such as lamps such as tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury xenon lamps, and carbon arc lamps, various lasers [e.g., semiconductor lasers, helium-neon lasers, argon ion lasers, helium cadmium lasers, and YAG (yttrium-aluminum-garnet) lasers], light-emitting diodes, and cathode ray tubes.

[0095] As a means for obtaining linearly polarized light, a method using a polarizing plate (e.g., an iodine polarizing plate, a dichroic material polarizing plate, and a wire grid polarizing plate), a method using a prism-based element (e.g., a Glan-Thompson prism) or a reflective polarizer using the Brewster angle, or a method using light emitted from a polarized laser light source can be adopted. Also, a filter or a wavelength conversion element may be used to selectively irradiate only light of a required wavelength.

[0096] In the case of linearly polarized light, the light is irradiated from the top or back surface of the alignment film perpendicularly or obliquely to the alignment film surface. The incident angle of the light varies depending on the photoalignment material, but is preferably 0 to 90° (perpendicular), and more preferably 40 to 90°. In the case of non-polarized light, the alignment film is irradiated with non-polarized light obliquely, preferably at an incident angle of 10 to 80°, more preferably at an incident angle of 20 to 60°, and even more preferably at an incident angle of 30 to 50°. The irradiation time is preferably from 1 minute to 60 minutes, and more preferably from 1 minute to 10 minutes.

[0097] When patterning is required, a method of irradiating light using a photomask the number of times required to form a pattern, or a method of writing a pattern by laser light scanning can be used.

[0098] <Orientation process> The alignment step is a step of aligning the dichroic material contained in the coating film. This results in the production of the polarizer of the present invention. In the alignment step, it is considered that the dichroic material is aligned along the liquid crystal compound aligned by the alignment film. The orientation step may include a drying treatment. By the drying treatment, components such as a solvent can be removed from the coating film. The drying treatment may be performed by leaving the coating film at room temperature for a predetermined time (for example, natural drying), or may be performed by heating and / or blowing air. Here, the dichroic material contained in the present composition may be aligned by the above-mentioned coating film forming step or drying treatment. For example, in an embodiment in which the present composition is prepared as a coating liquid containing a solvent, the coating film may be dried to remove the solvent from the coating film, whereby the dichroic material contained in the coating film may be aligned, thereby obtaining the polarizer of the present invention.

[0099] The alignment step preferably includes a heat treatment, which allows the dichroic material contained in the coating film to be more oriented, thereby increasing the degree of orientation of the resulting polarizer. From the viewpoint of manufacturability, the heat treatment temperature is preferably 10 to 250° C., more preferably 25 to 190° C. The heating time is preferably 1 to 300 seconds, more preferably 1 to 60 seconds.

[0100] The orientation step may include a cooling treatment carried out after the heating treatment. The cooling treatment is a treatment for cooling the coated film after heating to about room temperature (20 to 25°C). This allows the orientation of the dichroic material contained in the coated film to be more fixed, and the degree of orientation of the obtained polarizer becomes higher. The cooling means is not particularly limited and can be carried out by a known method. Through the above steps, the polarizer of the present invention can be obtained.

[0101] [Other steps] The present production method may include a step of curing the polarizer (hereinafter also referred to as a "curing step") after the above-mentioned alignment step. The curing step is carried out, for example, by heating and / or light irradiation (exposure), and among these, it is preferable that the curing step is carried out by light irradiation. The light source used for curing may be various light sources such as infrared light, visible light, or ultraviolet light, but ultraviolet light is preferred. In addition, ultraviolet light may be irradiated while heating during curing, or ultraviolet light may be irradiated through a filter that transmits only specific wavelengths. The exposure may be carried out in a nitrogen atmosphere. When the curing of the polarizer proceeds by radical polymerization, it is preferable to carry out the exposure in a nitrogen atmosphere, since inhibition of polymerization by oxygen is reduced.

[0102] [Laminate] The laminate of the present invention has a substrate, an alignment film provided on the substrate, and the above-mentioned polarizer of the present invention provided on the alignment film. The laminate of the present invention may further include a λ / 4 plate on the polarizer of the present invention. Furthermore, the laminate of the present invention may have a barrier layer between the polarizer of the present invention and the λ / 4 plate. Each layer constituting the laminate of the present invention will now be described.

[0103] [Base material] The substrate can be appropriately selected, and examples thereof include glass and polymer films. The light transmittance of the substrate is preferably 80% or more. When a polymer film is used as the substrate, it is preferable to use an optically isotropic polymer film. Specific examples and preferred aspects of the polymer are described in paragraph

[0013] of JP-A-2002-22942. In addition, even if it is a polymer that is easily generated birefringence such as conventionally known polycarbonate or polysulfone, it is also possible to use one in which the generation of birefringence is reduced by modifying the molecule described in WO-A-2000 / 26705.

[0104] [Alignment film] The alignment film is as described above, and therefore the description thereof will be omitted.

[0105] [Polarizer] The polarizer of the present invention is as described above, and therefore the description thereof will be omitted.

[0106] [λ / 4 plate] A "λ / 4 plate" is a plate having a λ / 4 function, specifically, a plate having the function of converting linearly polarized light of a certain wavelength into circularly polarized light (or circularly polarized light into linearly polarized light). For example, specific examples of the λ / 4 plate having a single layer structure include a stretched polymer film and a retardation film having an optically anisotropic layer having λ / 4 function provided on a support, and specific examples of the λ / 4 plate having a multilayer structure include a broadband λ / 4 plate formed by laminating a λ / 4 plate and a λ / 2 plate. The λ / 4 plate and the polarizer of the present invention may be provided in contact with each other, or another layer may be provided between the λ / 4 plate and the polarizer of the present invention. Such layers include an adhesive layer or a bonding layer for ensuring adhesion, and a barrier layer.

[0107] [Barrier Layer] When the laminate of the present invention includes a barrier layer, the barrier layer is provided between the polarizer of the present invention and the λ / 4 plate. When a layer other than the barrier layer (e.g., an adhesive layer or a bonding layer) is provided between the polarizer of the present invention and the λ / 4 plate, the barrier layer can be provided, for example, between the polarizer of the present invention and the other layer. The barrier layer is also called a gas barrier layer (oxygen barrier layer), and has the function of protecting the polarizer of the present invention from gases such as oxygen in the atmosphere, moisture, or compounds contained in adjacent layers. For the barrier layer, reference can be made to the descriptions in, for example, paragraphs

[0014] to

[0054] of JP 2014-159124 A, paragraphs

[0042] to

[0075] of JP 2017-121721 A, paragraphs

[0045] to

[0054] of JP 2017-115076 A, paragraphs

[0010] to

[0061] of JP 2012-213938 A, and paragraphs

[0021] to

[0031] of JP 2005-169994 A.

[0108] [Application] The laminate of the present invention can be used, for example, as a polarizing element (polarizing plate), for example, as a linear polarizing plate or a circular polarizing plate. When the laminate of the present invention does not have an optically anisotropic layer such as the λ / 4 plate, the laminate can be used as a linear polarizing plate. On the other hand, when the laminate of the present invention has the above-mentioned λ / 4 plate, the laminate can be used as a circular polarizing plate.

[0109] [Image display device] The image display device of the present invention has the above-mentioned polarizer of the present invention or the above-mentioned laminate of the present invention. The display element used in the image display device of the present invention is not particularly limited, and examples thereof include a liquid crystal cell, an organic electroluminescence (hereinafter abbreviated as "EL") display panel, and a plasma display panel. Among these, a liquid crystal cell or an organic EL display panel is preferred, and a liquid crystal cell is more preferred. That is, the image display device of the present invention is preferably a liquid crystal display device using a liquid crystal cell as a display element, or an organic EL display device using an organic EL display panel as a display element, and more preferably a liquid crystal display device.

[0110] [Liquid crystal display device] A preferred embodiment of the liquid crystal display device, which is one example of the image display device of the present invention, is a liquid crystal display device having the above-mentioned polarizer of the present invention and a liquid crystal cell, and more preferably a liquid crystal display device having the above-mentioned laminate of the present invention (not including a λ / 4 plate) and a liquid crystal cell. In the present invention, of the polarizing elements provided on both sides of the liquid crystal cell, it is preferable to use the laminate of the present invention as the front side polarizing element, and it is more preferable to use the laminate of the present invention as both the front side and the rear side polarizing elements. The liquid crystal cell constituting the liquid crystal display device will be described in detail below.

[0111] <Liquid crystal cell> The liquid crystal cell used in the liquid crystal display device is preferably in VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode, or TN (Twisted Nematic) mode, but is not limited to these. In a TN mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially horizontally when no voltage is applied, and are further aligned in a twisted manner at an angle of 60 to 120°. TN mode liquid crystal cells are most commonly used as color TFT (Thin Film Transistor) liquid crystal display devices, and are described in many publications. In a VA mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied. VA mode liquid crystal cells include (1) a narrow-sense VA mode liquid crystal cell (described in JP-A-2-176625) in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and substantially horizontally when voltage is applied, (2) a VA mode multi-domain (MVA mode) liquid crystal cell (described in SID97, Digest of tech. Papers (Proceedings) 28 (1997) 845) in order to expand the viewing angle, (3) a mode (n-ASM mode) liquid crystal cell in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and are aligned in a twisted multi-domain when voltage is applied (described in Proceedings of the Japan Liquid Crystal Discussion Society 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (announced at LCD International 98). In addition, the liquid crystal display may be of any of a PVA (Patterned Vertical Alignment) type, an optical alignment type, and a PSA (Polymer-Sustained Alignment) type. Details of these modes are described in detail in Japanese Patent Application Laid-Open No. 2006-215326 and Japanese Patent Application Laid-Open No. 2008-538819. In the IPS mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially parallel to the substrate, and the liquid crystal molecules respond in a planar manner when an electric field parallel to the substrate surface is applied. In the IPS mode, the black display is achieved when no electric field is applied, and the absorption axes of the pair of upper and lower polarizing plates are perpendicular to each other. Methods of reducing light leakage during black display in an oblique direction and improving the viewing angle using an optical compensation sheet are disclosed in JP-A-10-54982, JP-A-11-202323, JP-A-9-292522, JP-A-11-133408, JP-A-11-305217, JP-A-10-307291, and the like.

[0112] [Organic EL display device] A suitable embodiment of an organic EL display device, which is one example of the image display device of the present invention, includes, from the viewing side, the above-mentioned polarizer of the present invention, a λ / 4 plate, and an organic EL display panel, in this order. More preferably, the laminate of the present invention having a λ / 4 plate and an organic EL display panel are arranged in this order from the viewing side. In this case, the laminate is arranged in the following order from the viewing side: a substrate, an alignment film, the polarizer of the present invention, a barrier layer that is provided if necessary, and the λ / 4 plate. The organic EL display panel is a display panel configured using an organic EL element having an organic light-emitting layer (organic electroluminescence layer) sandwiched between electrodes (cathode and anode). The configuration of the organic EL display panel is not particularly limited, and a known configuration may be adopted. EXAMPLES

[0113] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0114] [Synthesis Example 1] The first dichroic material M1 was synthesized as follows.

[0115] [ka]

[0116] 12.6 g of 4-nitrophenol, 20.0 g of 9-bromononanol, and 13.8 g of potassium carbonate were dissolved in 30 ml of N,N-dimethylacetamide (DMAc) and stirred at an external temperature of 105°C for 2 hours. The temperature was lowered to room temperature, and the mixture was separated and washed with ethyl acetate and 10% aqueous ammonium chloride solution. The organic layer was dried over magnesium sulfate and then concentrated using a rotary evaporator to obtain a brown liquid (M1-1).

[0117] Next, 25 ml of DMAc was added to the obtained (M1-1) and stirred in an ice bath. While maintaining the temperature of the reaction system below 15°C, 9.5 g of propionyl chloride was added dropwise, and after the addition, the mixture was stirred at room temperature for 1 hour. Ethyl acetate-10% ammonium chloride aqueous solution was added for liquid separation and washing. After drying with magnesium sulfate, the mixture was concentrated using a rotary evaporator to obtain a brown liquid (M1-2).

[0118] 15.2g of Fe powder, 7.2g of ammonium chloride, 20ml of 2-propanol, and 10ml of water were mixed and refluxed at an external temperature of 105°C. A yellow solid (M1-2) dissolved by heating in 30ml of ethyl acetate was added dropwise to the refluxed system. After the addition was completed, the reaction was allowed to proceed for 30 minutes under reflux. After the temperature was lowered to room temperature, the iron powder was removed by celite filtration, the filtrate was separated into ethyl acetate and water, and the organic layer was washed three times with water. The organic layer was concentrated using a rotary evaporator, and 15 ml of THF (tetrahydrofuran) and 15 ml of ethyl acetate were added. A mixture of 240 ml of water and 20 ml of concentrated hydrochloric acid was added dropwise to this solution to obtain 15.3 g of the desired compound (M1-3). NMR (Nuclear Magnetic Resonance) data (DMSO-d6) δ: 1.03 (t, 3H), 1.25-1.48 (m, 11H), 1.58 (m, 2H), 1.7 1(m, 2H), 2.30(m, 2H), 3.97(m, 4H), 7.01(d, 2H), 7.29(d, 2H), 10.04(br-s, 3H)

[0119] 2-Aminothiophene hydrochloride was synthesized from 2-nitrothiophene according to the method described in the literature (Journal of Medicinal Chemistry, 2005, Vol. 48, p. 5794). 6.2 g of the (M1-3) obtained above was added to a mixture of 15 ml of 12 mol / L hydrochloric acid, 30 ml of water, and 30 ml of THF, cooled to an internal temperature of 5° C. or less, and 1.4 g of sodium nitrite dissolved in 9 ml of water was added dropwise. The mixture was stirred at an internal temperature of 5° C. or less for 1 hour to prepare a diazonium solution. Next, 2.4 g of 2-aminothiophene hydrochloride was dissolved in 12 ml of water and 6 ml of hydrochloric acid, and the diazonium solution prepared above was added dropwise at an internal temperature of 0° C. The reaction solution was allowed to warm to room temperature and was stirred for 2 hours. The precipitated solid was filtered and dried to obtain 6.3 g of a reddish orange solid (M1-4). NMR data (DMSO-d6) δ: 1.01(t, 3H), 1.29-1.40(m, 11H), 1.55(m, 2H), 1.69(m, 2H), 2.29(m , 2H), 3.17(s, 2H), 3.97(m, 4H), 6.88(br-s, 1H), 6.97(d, 2H), 7.39(d, 2H), 7.85(m, 1H) In the formula, "Boc" means a tert-butoxycarbonyl group.

[0120] 5.6 g of the (M1-4) obtained above was suspended and dissolved in 100 ml of acetic acid, and 1.5 g of sodium thiocyanate was added at room temperature. The mixture was cooled with water and 2.0 g of bromine was added dropwise while maintaining the internal temperature at 20°C or less. After stirring at room temperature for 2 hours, 100 ml of water was added, and the resulting solid was filtered and dried to obtain 5.3 g of a black solid (M1-5). NMR data (CDCl3)δ:1.14(t, 3H), 1.30-1.50(m, 11H), 1.60(m, 6H), 1.81(m, 2H), 2 .32(q, 2H), 4.04(m), 4H), 5.31(br, 2H), 6.95(d, 2H), 7.66(s, 1H), 7.78(d, 2H)

[0121] 4.7 g of the (M1-5) obtained above was added to 6 ml of hydrochloric acid and 6 ml of acetic acid, and 5 ml of an aqueous solution of 0.72 g of sodium nitrite was added dropwise at 0° C. or lower under ice cooling. After stirring for 1 hour, 0.52 mg of amidosulfuric acid was added to obtain a diazonium solution. The diazonium solution was added dropwise to a 10 ml methanol solution containing 2.2 g of N-ethyl-N-(2-acryloyloxyethyl)aniline, while maintaining the temperature below 0°C. The mixture was warmed to room temperature and stirred for 1 hour, after which 30 ml of water was added and the resulting solid was filtered off. The mixture was purified using a column to obtain 0.6 g of a black-green solid compound (first dichroic substance M1). N-ethyl-N-(2-acryloyloxyethyl)aniline was synthesized from N-ethylaniline as a raw material according to US Pat. No. 7,601,849 and known methods. NMR data (CDCl3)δ: 1.14 (t, 3H), 1.26 (t, 3H), 1.29 (br-s, 8H), 1.49 (m, 2H), 1.64 (m, 2H), 1.82 (m, 2H), 2.33 (m, 2H), 3.58 (m, 2H), 3.7 7(m, 2H), 4.07(m, 4H), 4.40(m, 2H), 5.90(dd, 1H), 6.15(dd, 1H), 6.40(dd, 1H), 6.82(d, 2H), 7.00(d, 2H), 7.88(m, 3H), 7.95(d, 2H)

[0122] [Synthesis Example 2] The second dichroic dye compound O1 was synthesized as follows.

[0123] [ka]

[0124] 27 g of p-acetylaminoaniline was added to 100 ml of water, cooled to 0°C, and stirred. 66 ml of concentrated hydrochloric acid was added dropwise to this solution. Next, an aqueous solution of 12.5 g of sodium nitrite (manufactured by Wako Pure Chemical Industries, Ltd.) dissolved in 30 ml of water was added dropwise. The internal temperature was kept at 0°C to 5°C. After the dropwise addition was completed, the mixture was stirred at 0°C or below for 1 hour to prepare a diazonium salt solution. 20 ml of methanol was added to 17.5 g of phenol, and the mixture was stirred to dissolve. An aqueous solution of 28.8 g of NaOH in 150 ml of water was added to this solution, cooled to 0°C, and stirred. The diazonium salt solution prepared by the above method was added dropwise to this solution at 0°C to 5°C. After the dropwise addition, the mixture was stirred at 5°C for 1 hour, and then stirred at room temperature for 1 hour to complete the reaction. Next, an aqueous solution of 36.0 g of NaOH in 150 ml of water was added, and the mixture was heated to reflux for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, and then an aqueous hydrochloric acid solution was added to adjust the pH to 7.0, and the precipitated crystals were filtered to obtain 40.2 g of compound O1-1 (yield: 87.2%, brown crystals).

[0125] N-ethyl-N-(2-acryloyloxyethyl)aniline was synthesized from N-ethylaniline as a raw material according to US Pat. No. 7,601,849 and known methods. 100 ml of acetic acid, 10 ml of water, and 20 ml of methanol were added to 5.0 g of compound O1-1, and the mixture was cooled to 0°C and stirred. 7 ml of concentrated hydrochloric acid was added dropwise to this solution. Then, an aqueous solution of 1.8 g of sodium nitrite dissolved in 5 ml of water was added dropwise. The internal temperature was kept at 0-5°C. After the dropwise addition, the mixture was stirred at 0°C or lower for 1 hour to prepare a diazonium salt solution. 7.7g of sodium acetate, 100ml of methanol, and 100ml of water were added to 8.4g of the N-ethyl-N-(2-acryloyloxyethyl)aniline synthesized above, and the mixture was stirred to dissolve, cooled to 0°C, and stirred. The diazonium salt solution prepared by the above method was added dropwise to this solution at 0-5°C. After the dropwise addition, the mixture was stirred at 5°C for 1 hour, and then stirred at room temperature for 1 hour to complete the reaction. The precipitated crystals were filtered to obtain 6.2g of compound O1-2 (yield: 86.8%, brown crystals).

[0126] 50.0 g of 1-bromononanol was dissolved in 500 ml of ethyl acetate, and then 26.5 g of triethylamine was added dropwise and stirred at 5°C. 22.8 g of propionyl chloride was added dropwise, and the mixture was stirred at room temperature for 1 hour to complete the reaction. After the reaction was completed, 175 ml of water was added and the mixture was separated, and then 10 g of magnesium sulfate was added to the organic layer and dehydrated. The obtained organic layer was concentrated using a rotary evaporator to obtain 9-bromononyl propionate (52 g, colorless transparent liquid).

[0127] Compound O1-2 (7.2 g), potassium carbonate (7.7 g, 0.014 mmol), potassium iodide (0.15 g, 0.002 mol) were added with 72 ml of dimethylacetamide and heated to 80 ° C. and stirred. 8.4 g of the above-synthesized 9-bromononyl propionate was added dropwise to this solution. After the dropwise addition, the mixture was heated to 80 ° C. and stirred for 4 hours to complete the reaction. After the reaction was completed, the reaction solution was poured into water, and the precipitated crystals were filtered and washed with water. The crystals were separated and purified by silica gel column chromatography (eluent: chloroform, then chloroform / ethyl acetate = 50 / 1 in that order). Methanol was added to the residue, and the precipitated crystals were filtered, washed with methanol, and dried. In this way, 5.5 g of the second dichroic substance O1 (orange crystals) was obtained. NMR data (CDCl3)δ: 1.13(t, 3H), 1.25(t, 3H), 1.29(br-s, 8H), 1.49(m, 2H), 1.64(m, 2H), 1.82(m, 2H), 2.33(q, 2H), 2.53(m, 2H), 2.73(t, 2H), 4.03(q, 4H), 4.38(t, 2H), 5.86(d, 1H), 6.12(dd, 1H), 6.43(d, 1H), 6.83(d, 2H), 7.00(d, 2H), 7.94(m, 8H)

[0128] [Synthesis Example 3] The third dichroic material Y1 was synthesized as follows. First, 4-hydroxybutyl acrylate (20 g) and mesyl chloride (16.8 g, MsCl) were dissolved in ethyl acetate (90 mL), and triethylamine (16.4 g, NEt3) was added dropwise while cooling in an ice bath. After stirring for 2 hours at room temperature, 1N HCl was added and the mixture was separated. The obtained organic layer was distilled under reduced pressure to obtain compound y1 (30 g) having the following structure.

[0129] [ka]

[0130] Then, the third dichroic material Y1 was synthesized according to the following route.

[0131] [ka]

[0132] First, compound y2 (10g) was synthesized according to the literature (Chem. Eur. J. 2004.10.2011). Compound y2 (10 g) was dissolved in water (300 mL) and hydrochloric acid (17 mL), cooled in an ice bath, sodium nitrite (3.3 g) was added, and the mixture was stirred for 30 minutes. Amidosulfuric acid (0.5 g) was further added, followed by m-toluidine (5.1 g) and stirring at room temperature for 1 hour. After stirring, the mixture was neutralized with hydrochloric acid, and the resulting solid was collected by suction filtration to obtain compound y2 (3.2 g). Compound y2 (1g) was dissolved in a THF solution consisting of tetrahydrofuran (30mL, THF), water (10mL), and hydrochloric acid (1.6mL), cooled in an ice bath, sodium nitrite (0.3g) was added, and the mixture was stirred for 30 minutes, after which amidosulfuric acid (0.5g) was further added. Separately, phenol (0.4g) was dissolved in potassium carbonate (2.76g) and water (50mL), cooled in an ice bath, and then the above THF solution was added dropwise and stirred at room temperature for 1 hour. After stirring, water (200mL) was added, and the obtained compound y3 (1.7g) was suction filtered. Compound y3 (0.6 g), compound y1 (0.8 g) and potassium carbonate (0.95 g) were dissolved in DMAc (30 mL, dimethylacetamide) and stirred for 3.5 hours at 90° C. After stirring, water (300 mL) was added, and the resulting solid was suction filtered to obtain a third dichroic substance Y1 (0.3 g).

[0133] [Synthesis Example 4] The polymer liquid crystal compound L1 was prepared by the following procedure.

[0134] (Synthesis of compound L1-2)

[0135] [ka]

[0136] 2-Chloroethoxyethoxyethanol (244 g) and potassium carbonate (200 g) were added to a solution (300 mL) of butylparaben (201 g) in N,N-dimethylformamide (DMF). After stirring at 95° C. for 9 hours, toluene (262 mL) and water (660 mL) were added, and concentrated hydrochloric acid (147 g) was added dropwise. After stirring for 10 minutes, the reaction solution was left to stand and washed by a separation operation. To the obtained organic layer, 28% by mass sodium methoxide methanol solution (500 g) and water (402 mL) were added, and the mixture was stirred at 50° C. for 2 hours. Thereafter, the organic solvent was distilled off by concentration, water (402 mL) was added, and concentration was performed again at 50° C. until the weight became 1.13 kg. Water (478 mL) was added to the obtained solution, and concentrated hydrochloric acid (278 g) was added dropwise. Ethyl acetate (1.45 kg) was added thereto, stirred at 30° C. for 10 minutes, and the aqueous layer was removed by a separation operation. Next, 20% by mass saline solution (960 mL) was added thereto, stirred at 30° C. for 10 minutes, and the aqueous layer was removed by a separation operation. N-methylpyrrolidone (824 g) was added to the obtained organic layer, and a concentration operation was performed at 70° C. for 4 hours, to obtain 1.13 kg of an N-methylpyrrolidone solution containing compound (L1-1). 1085 g of the obtained N-methylpyrrolidone solution containing (L1-1) was used to carry out the next step. N,N-dimethylaniline (189g) and 2,2,6,6-tetramethylpiperazine (1.5g) were added to the N-methylpyrrolidone (NMP) solution (1085g) containing the obtained (L1-1), and after cooling the internal temperature, acrylic acid chloride (122g) was added dropwise so that the internal temperature did not exceed 10°C. After stirring for 2 hours at an internal temperature of 10°C, methanol (81g) was added dropwise and stirred for 30 minutes. Ethyl acetate (1.66kg), 10% by mass saline (700mL) and 1N hydrochloric acid water (840mL) were added thereto, and the aqueous layer was removed by a liquid separation operation. Next, 10% by mass saline solution (800mL) was added, and the mixture was stirred at 30°C for 10 minutes, and the aqueous layer was removed by a liquid separation operation. Next, 20% by mass saline solution (800mL) was added, and the mixture was stirred at 30°C for 10 minutes, and the aqueous layer was removed by a liquid separation operation. A mixed solvent of hexane / isopropyl alcohol (1780 mL / 900 mL) was added to the obtained organic layer, cooled to 5°C, stirred for 30 minutes, and then filtered to obtain 209 g of a white solid compound (L1-2) (3-step yield 65%). In the structural formula, Bu represents a butyl group.

[0137] 1 H-NMR (solvent: CDCl3) δ(ppm):3.67-3.78(m,6H),3.87-3.92(m,2H),4.18-4.23(m,2H),4.31-4.35(m, 2H),5.80-5.85(m,1H),6.11-6.19(m,1H),6.40-6.46(m,1H),6.93-6.98(m,2H),8.02-8.07(m,2H)

[0138] (Synthesis of compound L1-3)

[0139] [ka]

[0140] Dibutylhydroxytoluene (BHT) (200 mg) was added to a tetrahydrofuran (THF) solution (70 mL) of methanesulfonyl chloride (MsCl) (73.4 mmol, 5.7 mL), and the internal temperature was cooled to -5 ° C. Then, a THF solution of compound (L1-2) (66.7 mmol, 21.6 g) and diisopropylethylamine (DIPEA) (75.6 mmol, 13.0 mL) was added dropwise so that the internal temperature did not rise above 0 ° C. After stirring for 30 minutes at -5 ° C, N,N-dimethyl-4-aminopyridine (DMAP) (200 mg) was added, and a tetrahydrofuran (THF) and dimethylacetamide (DMAc) solution of diisopropylethylamine (75.6 mmol, 13.0 mL) and 4-hydroxy-4'-methoxybiphenyl (60.6 mmol, 12.1 g) was added dropwise so that the internal temperature did not rise above 0 ° C. The mixture was then stirred at room temperature for 4 hours. Methanol (5 mL) was added to stop the reaction, and water and ethyl acetate were then added. The organic layer extracted with ethyl acetate was stripped of the solvent using a rotary evaporator, and the mixture was purified by column chromatography using ethyl acetate and hexane to obtain 18.7 g (61% yield) of compound (L1-3) as a white solid. In the structural formula, Me represents a methyl group.

[0141] 1 H-NMR (solvent: CDCl3) δ(ppm):3.65-3.82(m,6H),3.85(s,3H),3.85-3.95(m,2H),4.18-4.28(m,2H),4.28-4.40(m,2H),5 .82(dd,1H),6.15(dd,1H),6.43(dd,1H),6.90-7.05(m,4H),7.20-7.30(m,2H),7.45-7.65(m,4H),8.10-8.20(m,2H)

[0142] The impurities include the following compound (L1-b).

[0143] [ka]

[0144] (Synthesis of compound L1-23)

[0145] [ka]

[0146] Methyl 4-(4-hydroxyphenyl)benzoate was synthesized according to the method described in Journal of Polymer Science, Part A: Polymer Chemistry, 2012, vol. 50, pp. 3936-3943.

[0147] 2,2,6,6-Tetramethylpiperidine 1-oxyl (68 mg) was added to a solution (44 mL) of methanesulfonyl chloride (MsCl) (54.8 mmol, 6.27 g) in ethyl acetate, and the internal temperature was cooled to -5 ° C. Then, a THF solution of compound (L1-2) (52.6 mmol, 17.1 g) synthesized as described above and diisopropylethylamine (DIPEA) (57.0 mol, 7.36 g) was added dropwise so that the internal temperature did not rise above 0 ° C. After stirring for 30 minutes at -5 ° C., a DMAc solution of methyl 4-(4-hydroxyphenyl)benzoate (43.8 mmol, 10.0 g) and N-methyl-imidazole (NMI) (1.8 g) were added, and diisopropylethylamine (75.6 mmol, 13.0 mL) was added dropwise so that the internal temperature did not rise above 0 ° C. Then, the mixture was stirred at room temperature for 4 hours. The reaction was stopped by adding water and ethyl acetate. The organic layer was separated and extracted with ethyl acetate. The solvent was removed using a rotary evaporator. The organic layer was purified by column chromatography using ethyl acetate and hexane to obtain 20.4 g (yield 87%) of a white solid compound (L1-23).

[0148] 1H-NMR (solvent: CDCl3) δ(ppm):3.68-3.80(m,6H),3.87-3.95(m,2H),3.95(s,3H),4.20-4.27(m,2H),4.31-4.37(m,2H),5 .83(dd,1H),6.16(dd,1H),6.43(dd,1H),6.97-7.05(m,2H),7.28-7.35(m,2H),7.64-7.72(m,4H),8.08-8.20(m,4H)

[0149] Impurities include the following compound (L1-b2).

[0150] [ka]

[0151] (Synthesis of polymer liquid crystal compound L1)

[0152] [ka]

[0153] Compound (L1-3) (84 g), compound (L1-23) (21 g), and dibutylhydroxytoluene (BHT) (158 mg) were dissolved in anisole (337 g). 2,2'-azobis(2-methylpropionate)dimethyl (1660 mg) (product name "V-601") was added thereto at room temperature and stirred. The obtained anisole solution was dropped into anisole (84 g) that had been heated to 80°C under a nitrogen atmosphere over a period of 2 hours, and after the dropwise addition was completed, the mixture was stirred at 80°C for 4 hours. The obtained reaction solution was dropped into methanol (1080 mL), and the precipitate was collected by filtration, and the residue was washed with acetonitrile to obtain 100 g (yield 95%) of a white solid compound (polymer liquid crystal compound L1). The weight average molecular weight (Mw) of the obtained polymer liquid crystal compound L1 was 13,300. The molecular weight was calculated in terms of polystyrene by gel permeation chromatography (GPC), three TOSOH TSKgelSuperAWM-H columns (manufactured by Tosoh Corporation) were connected together, and N-methylpyrrolidone was used as the solvent.

[0154] [Example 1] [Preparation of transparent support 1] An alignment film coating solution having the following composition was continuously applied onto a 40 μm-thick TAC substrate (product name "TG40", manufactured by Fujifilm Corporation) using a #8 wire bar. After that, it was dried for 2 minutes with hot air at 100°C to obtain a transparent support 1 in which a 0.8 μm-thick polyvinyl alcohol (PVA) alignment film was formed on the TAC substrate. The modified polyvinyl alcohol was added to the alignment film coating solution so that the solid content concentration was 4% by mass. ---------------------------------------------------------------------------------- Composition of alignment film coating solution ---------------------------------------------------------------------------------- The following modified polyvinyl alcohols 70 parts by mass of water Methanol 30 parts by weight ----------------------------------------------------------------------------------

[0155] Modified Polyvinyl Alcohol

[0156] [ka]

[0157] [Preparation of Alignment Film 1] To 1 part by mass of photoalignment material E-1 having the following structure, 41.6 parts by mass of butoxyethanol, 41.6 parts by mass of dipropylene glycol monomethyl, and 15.8 parts by mass of pure water were added, and the resulting solution was pressure-filtered through a 0.45 μm membrane filter to prepare composition 1 for forming an alignment film. Next, the obtained composition 1 for forming an alignment film was applied onto a transparent support 1 and dried at 60° C. for 1 minute. Thereafter, the obtained coating film was irradiated with linearly polarized ultraviolet light (illuminance 4.5 mW, irradiation amount 500 mJ / cm 2 ) using a polarized ultraviolet light exposure device. 2 ) was irradiated to prepare an alignment film 1 (referred to as azo (E-1) in Table 1 below).

[0158] [ka]

[0159] [Preparation of Polarizer 1] Onto the obtained alignment film 1, the following composition 1 for forming a polarizer was continuously applied with a #7 wire bar to form a coating film 1. Next, the coating film 1 was heated at 140° C. for 90 seconds, and then cooled to room temperature (23° C.). It was then heated at 90° C. for 60 seconds and cooled again to room temperature. Then, a high-pressure mercury lamp was used to illuminate the area at an intensity of 28 mW / cm 2 By irradiating the film for 60 seconds under the irradiation conditions above, a polarizer 1 (film 1) was formed on the alignment film 1. ------------------------------------------------------------------ Composition of polarizer-forming composition 1 ------------------------------------------------------------------ 0.555 parts by mass of the following first dichroic material M1 0.205 parts by mass of the second dichroic material O1 below 0.128 parts by mass of the third dichroic material Y1 below 4.032 parts by mass of the following polymer liquid crystal compound L1 0.039 parts by mass of the following interface improver F1 Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass Cyclopentanone 66.500 parts by mass Tetrahydrofuran 28.500 parts by mass ------------------------------------------------------------------

[0160] [ka] JPEG0007607728000024.jpg11100 JPEG0007607728000025.jpg11121 JPEG0007607728000026.jpg25104 JPEG0007607728000027.jpg9110

[0161] [Formation of transparent resin layer (barrier layer) 1] The following curable composition 1 was continuously applied onto the polarizer 1 using a #2 wire bar, and dried at 60° C. for 5 minutes. Then, a high-pressure mercury lamp was used to illuminate the area at an intensity of 28 mW / cm 2 The curable composition 1 was cured by irradiation under the irradiation conditions of for 60 seconds, thereby producing a laminate in which a transparent resin layer (barrier layer) 1 was formed on a polarizer 1. In this manner, the laminate of Example 1 was obtained. A cross section of the transparent resin layer 1 was cut using a microtome cutter, and the film thickness was measured by observation with a scanning electron microscope (SEM), and was found to be approximately 1.0 μm.

[0162] ------------------------------------------------------------------ Curable composition 1 ------------------------------------------------------------------ Polymerizable compound KAYARAD PET-30 (manufactured by Nippon Kayaku Co., Ltd.) 29 parts by mass Polymerization initiator: IRGACURE819 (BASF) 1 part by weight Alumina ethanol sol A2K5-10 (Kawaken Fine Chemicals Co., Ltd., columnar alumina hydrate particles dispersed in liquid) Colloidal liquid) 70 parts by weight ------------------------------------------------------------------

[0163] KAYARAD PET-30

[0164] [ka]

[0165] [Examples 2 to 19, Comparative Examples 1 to 2] A laminate having a polarizer was produced in the same manner as in Example 1, except that a polarizer-forming composition having the composition shown in Table 1 was used instead of the polarizer-forming composition 1.

[0166] [Polymer liquid crystal compound] The components used in each example are listed below.

[0167] [ka]

[0168] [ka]

[0169] The maximum absorption wavelength of the first dichroic substance M is shown below. M1: 591 nm M2: 591 nm M3: 592 nm M4: 589 nm M5: 608 nm M6: 592 nm M7: 591 nm M8: 590 nm M9: 604 nm

[0170] [ka]

[0171] The maximum absorption wavelength of the second dichroic substance M is shown below. O1: 471 nm O2: 484 nm O3: 455 nm O4: 459 nm O5: 471 nm O6: 488 nm O7: 471 nm O8: 478 nm O9: 477 nm O10: 479 nm O11: 477 nm O12: 472 nm O13: 460 nm O14: 467 nm O15: 477 nm O16: 460 nm O17: 484 nm

[0172] [ka]

[0173] The maximum absorption wavelength of the third dichroic substance Y is shown below. Y1: 418 nm Y2: 418 nm Y3: 447 nm

[0174] [ka]

[0175] [evaluation] The polarizers of the Examples and Comparative Examples obtained as described above were evaluated as follows.

[0176] [Orientation] With a linear polarizer inserted into the light source side of an optical microscope (Nikon Corporation, product name "ECLIPSE E600 POL"), each laminate of the examples and comparative examples was set on the sample stage, and the absorbance of the polarizer in the wavelength range of 380 nm to 780 nm was measured at 1 nm intervals using a multichannel spectrometer (Ocean Optics, product name "QE65000"), and the degree of orientation was calculated as the average value in the range of 400 nm to 700 nm using the following formula. The results are shown in Table 1. Orientation degree: S=((Az0 / Ay0)-1) / ((Az0 / Ay0)+2) Az0: Absorbance for polarized light in the absorption axis direction of the polarizer Ay0: Absorbance for polarized light in the direction of the polarization axis of the polarizer

[0177] [Maximum absorption wavelength] <Maximum absorption wavelength in Example 1> (Membrane 1-2) On the alignment film 1 obtained above, the following composition 1-2 for forming a polarizer was continuously applied with a #7 wire bar to form a coating film 1-2. Next, the coating film 1-2 was heated at 140° C. for 90 seconds, and then the coating film 1-2 was cooled to room temperature (23° C.). It was then heated at 80° C. for 60 seconds and cooled again to room temperature. Then, a high-pressure mercury lamp was used to illuminate the area at an intensity of 28 mW / cm 2 The film was irradiated for 60 seconds under the irradiation conditions described above to prepare film 1-2. Film 1-2 does not contain the first dichroic material M1. ------------------------------------------------------------------ Composition of polarizer forming composition 1-2 ------------------------------------------------------------------ Second dichroic material O1 0.231 parts by weight Third dichroic material Y1 0.144 parts by weight Polymer liquid crystal compound L1 4.544 parts by mass Interface improver F1 0.039 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass Cyclopentanone 66.500 parts by mass Tetrahydrofuran 28.500 parts by mass ------------------------------------------------------------------

[0178] (Membrane 1-4) On the alignment film 1 obtained above, the following composition for forming a polarizer 1-4 was continuously applied with a #7 wire bar to form a coating film 1-4. Next, the coating film 1-4 was heated at 140° C. for 90 seconds, and the coating film 1-2 was cooled to room temperature (23° C.). It was then heated at 90° C. for 60 seconds and cooled again to room temperature. Then, a high-pressure mercury lamp was used to illuminate the area at an intensity of 28 mW / cm 2 The film was irradiated for 60 seconds under the irradiation conditions described above to prepare film 1-4. Film 1-4 does not contain the second dichroic material O1. ------------------------------------------------------------------ Composition of polarizer forming composition 1-4 ------------------------------------------------------------------ First dichroic material M1 0.577 parts by weight Third dichroic material Y1 0.143 parts by mass Polymer liquid crystal compound L1 4.198 parts by mass Interface improver F1 0.039 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass Cyclopentanone 66.500 parts by mass Tetrahydrofuran 28.500 parts by mass ------------------------------------------------------------------

[0179] (Method for measuring maximum absorption wavelength) For the absorption spectra of polarizer 1 (film 1), film 1-2, and film 1-4 in Example 1, the absorbance in the wavelength range of 380 to 800 nm was measured at 1 nm pitch, and the absorbance (Abs) at every 1 nm pitch was calculated using the following formula to obtain the absorption spectrum for each film. Abs = Az0 / (1 + 2 × S) Based on the obtained absorption spectra, the maximum absorption wavelength λ1 of the absorption spectrum of polarizer 1, the maximum absorption wavelength λ2 of the absorption spectrum of film 1-2, and the maximum absorption wavelength λ4 of the absorption spectrum of film 1-4 were obtained. In addition, the maximum absorption wavelength λ of the difference spectrum obtained by subtracting the absorption spectrum of film 1-4 from the absorption spectrum of polarizer 1 was obtained. The results are shown in Table 1.

[0180] <Maximum absorption wavelength in Examples 2 to 31 and Comparative Examples 1 and 2> In the same manner as in Example 1, corresponding films were prepared for each of the examples and comparative examples, and the maximum absorption wavelength λ1, the maximum absorption wavelength λ2, the maximum absorption wavelength λ4, and the maximum absorption wavelength λ of the difference spectrum were obtained. The results are shown in Tables 1 and 2.

[0181] <Examples 32 to 33, Comparative Example 3> A glass substrate (Central Glass Co., Ltd., soda lime glass, size 300 mm×300 mm, thickness 1.1 mm) was washed with an alkaline detergent, and then pure water was poured into the glass substrate, followed by drying. The following composition for forming an alignment film was applied onto the dried glass substrate using a bar #12, and the applied composition for forming an alignment film 2 was dried at 110°C for 2 minutes to form a coating film on the glass substrate. The resulting coating film was subjected to a rubbing treatment (number of roller revolutions: 1000 revolutions / spacer thickness: 2.9 mm, stage speed: 1.8 m / min) once to prepare an alignment film 2 on the glass substrate.

[0182] ---------------------------------------------------------------------------------- Composition of composition 2 for forming alignment film ---------------------------------------------------------------------------------- Modified vinyl alcohol (see formula (PVA-1) below) 2.00 parts by weight Water 74.08 parts by mass Methanol 23.86 parts by mass Photoinitiator (IRGACURE2959, manufactured by BASF) 0.06 parts by mass ----------------------------------------------------------------------------------

[0183] [ka]

[0184] A piece of 30 mm x 30 mm was cut out from the obtained alignment film 2, and a polarizer-forming composition 32 (containing a first dichroic material and a second dichroic material) shown in Table 3 below was spin-coated at 800 rpm to form a coating film. The coated film was dried at room temperature for 30 seconds and then heated at 130° C. for 15 seconds. Next, the coated film was cooled to room temperature, and then heated to 90° C. and cooled to room temperature to prepare a polarizer 32 (film 32). In addition, film 32-2 was prepared in a similar manner, except that polarizer-forming composition 32-2 (containing a second dichroic material and not containing a first dichroic material) described in Table 3 was used instead of polarizer-forming composition 32. In addition, film 32-4 was prepared in a similar manner, except that polarizer-forming composition 32-4 (containing a first dichroic material and not containing a second dichroic material) described in Table 3 was used instead of polarizer-forming composition 32. Except for using a polarizer-forming composition having the composition shown in Table 3, a laminate having polarizer 33 of Example 33, and films 33-2 and 33-4 corresponding to polarizer 33 (film 33), as well as a laminate having polarizer 3B (film 3B) of Comparative Example 3, and films 3B-2 and 3B-4 corresponding to polarizer 3B, were prepared following procedures similar to those of Example 32. The maximum absorption wavelength λ1, the maximum absorption wavelength λ2, the maximum absorption wavelength λ4, and the maximum absorption wavelength λ of the difference spectrum were then determined. The results are shown in Table 3.

[0185] [ka] JPEG0007607728000036.jpg30127

[0186] [XRD spectrum] <XRD spectrum of Example 1> Films 1-2 and 1-3 were prepared for the measurement of the XRD spectrum in Example 1. The method for preparing film 1-2 was as explained in the measurement of the maximum absorption wavelength. (Membrane 1-3) Film 1-3 was prepared in the same manner as Polarizer 1 except that the following composition for forming a polarizer 1-3 was used, and did not contain the first dichroic material M1 or the second dichroic material O1. ------------------------------------------------------------------ Composition of polarizer forming composition 1-3 ------------------------------------------------------------------ Third dichroic material Y1 0.151 parts by mass Polymer liquid crystal compound L1 4.768 parts by mass Interface improver F1 0.039 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.043 parts by mass Cyclopentanone 66.500 parts by mass Tetrahydrofuran 28.500 parts by mass ------------------------------------------------------------------ (Method of measuring XRD spectrum) The XRD spectra were measured for the polarizer 1, film 1-2, and film 1-3 of Example 1. The obtained film (polarizer) was cut to a size of 40 mm x 40 mm, and the polarizer surface was irradiated with X-rays under the following conditions using an X-ray diffraction device for thin film evaluation (manufactured by Rigaku Corporation, product name: "SmartLab") to perform in-plane XRD.

[0187] Using Cu radiation source (CuKα, output 45kV, 200mA) X-ray incident angle 0.2° Optical system used: Parallel optical system (CBO (Cross Beam Optics) (PB (Parallel Beam)) Incident side Incident slit 0.2mm Incident parallel slit In-plane PSC (Parallel Slit Collimator) 0.5deg (degree), length limiting slit 10mm Receiving side Receiving slit 20 mm, receiving parallel slit In-plane PSA (Parallel Slit Analyzer) 0.5 deg 2θχ / φ scan Scan conditions: 1 to 40 degrees, 0.008 degrees / step, 2.0 degrees / min φ scan Scan conditions: -120 to 120 degrees in 0.5 degree / step, 9.6 degree / min

[0188] The direction in which the polymer liquid crystal and dichroic material were aligned in the long axis direction was set as an azimuth angle (φ) of 0°, and in-plane measurements (2θχ / φ scans) were performed in all directions at 15° intervals. The φ scans performed on the observed peaks were used to determine the direction in the substrate plane with the highest peak intensity. Both measurements were performed using CuKα at an incidence angle of 0.20°. The peaks obtained from the measurements of the alignment direction (the direction determined as described above) were used to determine the periodic length from the relationship between the diffraction angle and distance shown below. In addition, the peak intensity was calculated (in cps) by normalizing it as the film thickness equivalent to the X-ray penetration length at an X-ray incidence angle of 0.2°. d=λ / (2×sinθ) (d: distance, λ: incident X-ray wavelength (CuKα; 1.54Å)) In the film 1-3, in the 0° direction (the direction determined as described above), peaks were observed at 2θ positions of 2.8° (periodic length: 31.6 Å), 4.9° (periodic length: 18.1 Å), and 7.9° (periodic length: 11.6 Å) (see FIG. 5). In contrast, in the film 1-2, in the 0° direction (the direction determined as described above), in addition to peaks at positions 2.8° (periodic length: 31.6 Å), 4.9° (periodic length: 18.1 Å), and 7.9° (periodic length: 11.6 Å), a peak was observed at position 6.0° (periodic length: 14.7 Å) (see FIG. 4). This shows that the peak at 6.0° is a peak derived from the second dichroic material O1. The peak intensity of this peak was 530. In contrast, in polarizer 1, peaks were observed at 2.8° (periodic length: 31.6 Å), 4.9° (periodic length: 18.1 Å), and 7.9° (periodic length: 11.6 Å) (see Figure 6), and the peak at 6.0° observed in film 1-2 was not observed. From this, it is inferred that in polarizer 1, the peak of the second dichroic material O1 disappears because the first dichroic material and the second dichroic material form an ordered structure (more specifically, a crystal structure).

[0189] <XRD Spectra of Examples 2 to 31 and Comparative Examples 1 to 2> In the same manner as in Example 1, corresponding films were prepared for each of the Examples and Comparative Examples, and the state of the peak originating from the second dichroic material O in the polarizer was observed. As a result, in the polarizers of Examples 2 to 31, the peak derived from the second dichroic material O disappeared or had a smaller peak intensity derived from the second dichroic material O in the corresponding films (i.e., films not containing the first dichroic material M but containing the second dichroic material O). Therefore, it is presumed that the first dichroic material and the second dichroic material form an ordered structure (more specifically, a crystal structure) in the polarizers of Examples 2 to 31. In contrast, the peak intensities resulting from the second dichroic material O in the polarizers of Comparative Examples 1 and 2 were equivalent to the peak intensities resulting from the second dichroic material O in the corresponding films (i.e., films that did not contain the first dichroic material M but contained the second dichroic material O). Therefore, it is inferred that the first dichroic material and the second dichroic material did not form an ordered structure in the polarizers of the Comparative Examples.

[0190] Next, a film 2-4 was produced in the same manner as in the polarizer 1, except that the following polarizer-forming composition 2-4 was used. The film 2-4 contains a first dichroic material M1 but does not contain a second dichroic material O1. ------------------------------------------------------------------ Composition of polarizer forming composition 2-4 ------------------------------------------------------------------ First dichroic material M1 0.540 parts by weight Third dichroic material Y1 0.153 parts by mass Polymer liquid crystal compound L1 5.210 parts by mass Interface improver F1 0.047 parts by mass Polymerization initiator IRGACURE819 (BASF) 0.051 parts by mass Cyclopentanone 66.500 parts by mass Tetrahydrofuran 28.500 parts by mass ------------------------------------------------------------------

[0191] The obtained films 2, 2-2, 2-3 and 2-4 were similarly subjected to in-plane measurements (2θχ / φ scans) in all directions at 15° increments, and the directions in the substrate plane with the highest peak intensity were determined by φ scans performed on the observed peaks. In the 57° direction (the orientation determined as described above), no peaks were observed at 2θ below 17° in film 2-4 (a film containing a first dichroic material but not a second dichroic material), film 2-2 (a film containing no first dichroic material but a second dichroic material), and film 2-3 (a film containing neither the first dichroic material nor the second dichroic material) (see Figures 7, 8, and 9). In contrast, in film 2 (film containing the first dichroic material and the second dichroic material), a peak was observed at 2θ of 3.1° (periodic length: 28.4 Å) (see FIG. 10). The peak intensity of this peak was 560. From this, it can be determined that the peak at 2θ of 3.1° (periodic length: 28.4 Å) is the peak of the crystal structure of the first dichroic material and the second dichroic material. Therefore, from this point of view, it is presumed that the first dichroic material and the second dichroic material form an array structure (more specifically, a crystal structure) in the film 2.

[0192] [Stabilization energy] For the polarizers of Examples 1, 4 to 7, 12 to 15, 20 to 31 and Comparative Example 1, the stabilization energy (unit: kcal / mol) and the stabilization energy ratio were calculated using AMBER11 according to the calculation method described above. The smaller the stabilization energy, the more favorably the arrangement structure of the first dichroic material and the second dichroic material is formed. The calculation results of the stabilization energy and the stabilization energy ratio are shown in Table 4. In the above-mentioned calculation method, the first dichroic material corresponds to dichroic material A, and the second dichroic material corresponds to dichroic material B.

[0193] [Table 1]

[0194] [Table 2]

[0195] [Table 3]

[0196] [Table 4]

[0197] The logP difference in Tables 1 and 2 means the difference in logP value between the group corresponding to R1 in formula (1) and the group corresponding to R4 in formula (2), where the first dichroic substance M has a structure represented by formula (1) and the second dichroic substance O has a structure represented by formula (2).

[0198] According to the measurement results of the maximum absorption wavelength described above, it is inferred that the first dichroic material and the second dichroic material form an association in the polarizer of the embodiment. According to the measurement results of the XRD spectrum, it is inferred that the first dichroic material and the second dichroic material form a crystal structure in the polarizer of the embodiment. From this, it can be said that the first dichroic material and the second dichroic material form an array structure in the polarizer of the embodiment. Thus, according to the polarizer of the embodiment in which the first dichroic material and the second dichroic material form an array structure, as shown in the evaluation results in Table 1, it was shown that the polarizer of the embodiment in which the first dichroic material and the second dichroic material form an array structure has a higher degree of orientation than the polarizer of the comparative example. [Explanation of symbols]

[0199] P polarizer M (of the first dichroic substance) molecule O (of the second dichroic substance) molecule L (liquid crystal compound) molecule G aggregate w width a Angle

Claims

1. A polarizer formed from a composition for forming a polarizer, the composition containing a liquid crystal compound and one of a first dichroic substance and one of a second dichroic substance, the first dichroic substance and the second dichroic substance satisfying the following conditions 1 and 2: the first dichroic material is a compound represented by formula (1), A polarizer, wherein the second dichroic material is a compound represented by formula (2): Condition 1: The absolute value of the difference between the log P value of R1 in formula (1) and the log P value of R4 in formula (2) is 2.30 or less. Condition 2: the sum of the energy of a state in which one molecule of the first dichroic material in a supercell of the first dichroic material is replaced with one molecule of the second dichroic material and the energy of one molecule of the first dichroic material is denoted as X1; When the sum of the energy of a supercell composed only of the first dichroic material before being replaced with one molecule of the second dichroic material and the energy of one molecule of the second dichroic material is X2, The stabilization energy ratio, which is the ratio of X1 to X2, is 0.22 to 1.

50. 【Chemistry 1】 In formula (1), Ar1 and Ar2 each independently represent a phenylene group which may have a substituent, or a naphthylene group which may have a substituent; R1 represents a hydrogen atom, a linear or branched alkyl group having 1 to 20 carbon atoms which may have a substituent, an alkoxy group, an alkylthio group, an alkylsulfonyl group, an alkylcarbonyl group, an alkyloxycarbonyl group, an acyloxy group, an alkylcarbonate group, an alkylamino group, an acylamino group, an alkylcarbonylamino group, an alkoxycarbonylamino group, an alkylsulfonylamino group, an alkylsulfamoyl group, an alkylcarbamoyl group, an alkylsulfinyl group, an alkylureido group, an alkylphosphoric acid amide group, an alkylimino group, or an alkylsilyl group; R2 and R3 each independently represent a linear or branched alkyl group having 1 to 20 carbon atoms which may be substituted with an acryloyloxy group. 【Chemistry 2】 In formula (2), n represents 1 or 2; Ar3 and Ar4 each independently represent a phenylene group which may have a substituent. Ar5 represents a phenylene group which may have a substituent, a naphthylene group which may have a substituent, or a heterocyclic group which may have a substituent; R4 represents a hydrogen atom, a linear or branched alkyl group having 1 to 20 carbon atoms which may have a substituent, an alkoxy group, an alkylthio group, an alkylsulfonyl group, an alkylcarbonyl group, an alkyloxycarbonyl group, an acyloxy group, an alkylcarbonate group, an alkylamino group, an acylamino group, an alkylcarbonylamino group, an alkoxycarbonylamino group, an alkylsulfonylamino group, an alkylsulfamoyl group, an alkylcarbamoyl group, an alkylsulfinyl group, an alkylureido group, an alkylphosphoric acid amide group, an alkylimino group, or an alkylsilyl group; R5 and R6 each independently represent a hydrogen atom, a linear or branched alkyl group having 1 to 20 carbon atoms which may have a substituent, an alkenyl group, an alkoxy group, an acyl group, an alkyloxycarbonyl group, an alkylamide group, an alkylsulfonyl group, an aryl group, an arylcarbonyl group, an arylsulfonyl group, an aryloxycarbonyl group, or an arylamide group, and R5 and R6 may be bonded to each other to form a ring. However, when R4 represents an alkyl group, at least one carbon atom of the alkyl group in R4 is -O-, -CO-, -C(O)-O-, -O-C(O)-, -Si(CH 3 ) 2 -O-Si(CH 3 ) 2 -, -N(R1')-, -N(R1')-CO-, -CO-N(R1')-, -N(R1')-C(O)-O-, -O-C(O)-N(R1')-, -N(R1')-C(O)-N(R1')-, -CH=CH-, -C≡C-, -N=N-, -C(R1')=CH-C(O)- or -O-C(O)-O-. R1' represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms. When a plurality of R1's are present in each group, they may be the same or different.

2. 2. The polarizer according to claim 1, wherein the stabilization energy ratio is from 0.40 to 1.

30.

3. a maximum absorption wavelength λ2 in an absorption spectrum of a film formed from a composition that does not contain the first dichroic material and contains the second dichroic material and the liquid crystal compound; and a maximum absorption wavelength λ in a difference spectrum between an absorption spectrum of the polarizer and an absorption spectrum of a film formed from a composition that does not contain the second dichroic material and contains the first dichroic material and the liquid crystal compound; and The polarizer according to claim 1 or 2, wherein the absolute value of the difference is greater than 2 nm.

4. a maximum absorption wavelength λ4 in an absorption spectrum of a film formed from a composition that does not contain the second dichroic material and contains the first dichroic material and the liquid crystal compound; and The maximum absorption wavelength λ1 in the absorption spectrum of the polarizer; The polarizer according to any one of claims 1 to 3, wherein the absolute value of the difference is greater than 2 nm.

5. the intensity of a peak O1 of a periodic structure originating from the second dichroic material in an X-ray diffraction spectrum of the polarizer; and an intensity of a peak O2 of a periodic structure derived from the second dichroic material in an X-ray diffraction spectrum of a film formed from a composition that does not contain the first dichroic material and contains the second dichroic material and the liquid crystal compound; and The polarizer according to any one of claims 1 to 4, wherein

6. 6. The polarizer of claim 5, wherein a ratio of the intensity of peak O1 to the intensity of peak O2 is less than 1.

7. When the X-ray diffraction spectrum of the polarizer was measured, 7. The polarizer according to claim 1, wherein a peak OM of the periodic structure derived from the first dichroic material and the second dichroic material is detected at a diffraction angle different from a diffraction angle at which a peak M2 of the periodic structure derived from the first dichroic material is detected in an X-ray diffraction spectrum of a film formed from a composition that does not contain the second dichroic material and contains the first dichroic material and the liquid crystal compound, and a diffraction angle at which a peak O2 of the periodic structure derived from the second dichroic material is detected in an X-ray diffraction spectrum of a film formed from a composition that does not contain the first dichroic material and contains the second dichroic material and the liquid crystal compound.

8. 8. The polarizer according to claim 1, wherein a stabilization energy representing an energetic loss occurring when one of the first dichroic materials and the second dichroic material enters a structure in which the other dichroic material is independently aligned is less than 72 kcal / mol.

9. 9. The polarizer of claim 8, wherein the stabilization energy is 55 kcal / mol or less.

10. The polarizer according to claim 8 or 9, wherein the stabilization energy is 35 kcal / mol or less.

11. the first dichroic substance is a dichroic substance having a maximum absorption wavelength in the range of 560 nm to 700 nm, 11. The polarizer according to claim 1, wherein the second dichroic substance has a maximum absorption wavelength in the range of 455 nm or more and less than 560 nm.

12. 12. The polarizer according to claim 1, further comprising a third dichroic material having a maximum absorption wavelength in the range of 380 nm or more and less than 455 nm.

13. An image display device comprising the polarizer according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Light absorption anisotropic film, production method thereof, and liquid crystal display device using the same

    JP2011237513A

  • Polarizing film, circularly polarizing plate and their manufacturing method

    JP2013101328A

  • Polarizing film, circularly polarizing plate, and organic el image display device using these

    JP2013109090A

  • Polarization film, circular polarization plate and method for manufacturing the same

    JP2013210624A

  • Elliptically polarizing plate

    JP2017167517A